Laser-cavity locking utilizing beam ellipticity: accessing the 10−7 instability scale relative to cavity linewidth - Diorico, Fritz R; Zhutov, Artem; Hosten, Onur (Optica)
Frequency-stable lasers form the back bone of precision measurements in science and technology. Such lasers typically attain their stability through frequency locking to reference cavities. State-of-the-art locking performances to date had been achieved using frequency modulation based methods, complemented with active drift cancellation systems. We demonstrate an all passive, modulation-free laser-cavity locking technique (squash locking) that utilizes changes in spatial beam ellipticity for error signal generation, and a coherent polarization post-selection for noise resilience. By comparing two identically built proof-of-principle systems, we show a frequency locking instability of 5×10 −7 relative to the cavity linewidth at 10 s averaging. The results surpass the demonstrated performances of methods engineered over the last five decades, potentially enabling an advancement in the precision control of lasers, while creating avenues for bridging the performance gaps between industrial grade lasers with scientific ones due to the afforded simplicity and scalability.
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

RAF-like protein kinases mediate a deeply conserved, rapid auxin response - Kuhn, Andre; Roosjen, Mark; Mutte, Sumanth; Dubey, Shiv Mani; Carrillo Carrasco, Vanessa Polet; Boeren, Sjef; Monzer, Aline; Koehorst, Jasper; Kohchi, Takayuki; Nishihama, Ryuichi; Fendrych, Matyas; Sprakel, Joris; et al. (Cell)
The plant-signaling molecule auxin triggers fast and slow cellular responses across land plants and algae. The nuclear auxin pathway mediates gene expression and controls growth and development in land plants, but this pathway is absent from algal sister groups. Several components of rapid responses have been identified in Arabidopsis, but it is unknown if these are part of a conserved mechanism. We recently identified a fast, proteome-wide phosphorylation response to auxin. Here, we show that this response occurs across 5 land plant and algal species and converges on a core group of shared targets. We found conserved rapid physiological responses to auxin in the same species and identified rapidly accelerated fibrosarcoma (RAF)-like protein kinases as central mediators of auxin-triggered phosphorylation across species. Genetic analysis connects this kinase to both auxin-triggered protein phosphorylation and rapid cellular response, thus identifying an ancient mechanism for fast auxin responses in the green lineage.
Keywords: General Biochemistry; Genetics and Molecular Biology

Too much information? Males convey parasite levels using more signal modalities than females utilise - Pal, Arka; Joshi, Mihir; Thaker, Maria (Journal of Experimental Biology)
Elaborate sexual signals are thought to have evolved and be maintained to serve as honest indicators of signaller quality. One measure of quality is health, which can be affected by parasite infection. Cnemaspis mysoriensis is a diurnal gecko that is often infested with ectoparasites in the wild, and males of this species express visual (coloured gular patches) and chemical (femoral gland secretions) traits that receivers could assess during social interactions. In this paper, we tested whether ectoparasites affect individual health, and whether signal quality is an indicator of ectoparasite levels. In wild lizards, we found that ectoparasite level was negatively correlated with body condition in both sexes. Moreover, some characteristics of both visual and chemical traits in males were strongly associated with ectoparasite levels. Specifically, males with higher ectoparasite levels had yellow gular patches with lower brightness and chroma, and chemical secretions with a lower proportion of aromatic compounds. We then determined whether ectoparasite levels in males influence female behaviour. Using sequential choice trials, wherein females were provided with either the visual or the chemical signals of wild-caught males that varied in ectoparasite level, we found that only chemical secretions evoked an elevated female response towards less parasitised males. Simultaneous choice trials in which females were exposed to the chemical secretions from males that varied in parasite level further confirmed a preference for males with lower parasites loads. Overall, we find that although health (body condition) or ectoparasite load can be honestly advertised through multiple modalities, the parasite-mediated female response is exclusively driven by chemical signals.
Keywords: Insect Science; Molecular Biology; Animal Science and Zoology; Aquatic Science; Physiology; Ecology; Evolution; Behavior and Systematics

Developmental patterning function of GNOM ARF-GEF mediated from the cell periphery - Adamowski, Maciek; Matijevic, Ivana; Friml, Jiří (eLife)
The GNOM (GN) Guanine nucleotide Exchange Factor for ARF small GTPases (ARF-GEF) is among the best studied trafficking regulators in plants, playing crucial and unique developmental roles in patterning and polarity. The current models place GN at the Golgi apparatus (GA), where it mediates secretion/recycling, and at the plasma membrane (PM) presumably contributing to clathrin-mediated endocytosis (CME). The mechanistic basis of the developmental function of GN, distinct from the other ARF-GEFs including its closest homologue GNOM-LIKE1 (GNL1), remains elusive. Insights from this study largely extend the current notions of GN function. We show that GN, but not GNL1, localizes to the cell periphery at long-lived structures distinct from clathrin-coated pits, while CME and secretion proceed normally in gn knockouts. The functional GN mutant variant GN fewerroots , absent from the GA, suggests that the cell periphery is the major site of GN action responsible for its developmental function. Following inhibition by Brefeldin A, GN, but not GNL1, relocates to the PM likely on exocytic vesicles, suggesting selective molecular associations en route to the cell periphery. A study of GN-GNL1 chimeric ARF-GEFs indicates that all GN domains contribute to the specific GN function in a partially redundant manner. Together, this study offers significant steps toward the elucidation of the mechanism underlying unique cellular and development functions of GNOM.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

Classical ‘spin’ filtering with two degrees of freedom and dissipation - Varshney, Atul; Ghazaryan, Areg; Volosniev, Artem (Few-Body Systems)
Coupling of orbital motion to a spin degree of freedom gives rise to various transport phenomena in quantum systems that are beyond the standard paradigms of classical physics. Here, we discuss features of spin-orbit dynamics that can be visualized using a classical model with two coupled angular degrees of freedom. Specifically, we demonstrate classical ‘spin’ filtering through our model and show that the interplay between angular degrees of freedom and dissipation can lead to asymmetric ‘spin’ transport.
Keywords: Atomic and Molecular Physics; and Optics

Multi-modal cryo-EM reveals trimers of protein A10 to form the palisade layer in poxvirus cores - Datler, Julia; Hansen, Jesse; Thader, Andreas; Schlögl, Alois; Bauer, Lukas W; Hodirnau, Victor-Valentin; Schur, Florian KM (Nature Structural & Molecular Biology)
Poxviruses are among the largest double-stranded DNA viruses, with members such as variola virus, monkeypox virus and the vaccination strain vaccinia virus (VACV). Knowledge about the structural proteins that form the viral core has remained sparse. While major core proteins have been annotated via indirect experimental evidence, their structures have remained elusive and they could not be assigned to individual core features. Hence, which proteins constitute which layers of the core, such as the palisade layer and the inner core wall, has remained enigmatic. Here we show, using a multi-modal cryo-electron microscopy (cryo-EM) approach in combination with AlphaFold molecular modeling, that trimers formed by the cleavage product of VACV protein A10 are the key component of the palisade layer. This allows us to place previously obtained descriptions of protein interactions within the core wall into perspective and to provide a detailed model of poxvirus core architecture. Importantly, we show that interactions within A10 trimers are likely generalizable over members of orthopox- and parapoxviruses.
Keywords: Molecular Biology; Structural Biology

Rapid translocation of NGR proteins driving polarization of PIN-activating D6 protein kinase during root gravitropism - Kulich, Ivan; Schmid, Julia; Teplova, Anastasiia; Qi, Linlin; Friml, Jiří (eLife)
Root gravitropic bending represents a fundamental aspect of terrestrial plant physiology. Gravity is perceived by sedimentation of starch-rich plastids (statoliths) to the bottom of the central root cap cells. Following gravity perception, intercellular auxin transport is redirected downwards leading to an asymmetric auxin accumulation at the lower root side causing inhibition of cell expansion, ultimately resulting in downwards bending. How gravity-induced statoliths repositioning is translated into asymmetric auxin distribution remains unclear despite PIN auxin efflux carriers and the Negative Gravitropic Response of roots (NGR) proteins polarize along statolith sedimentation, thus providing a plausible mechanism for auxin flow redirection. In this study, using a functional NGR1-GFP construct, we visualized the NGR1 localization on the statolith surface and plasma membrane (PM) domains in close proximity to the statoliths, correlating with their movements. We determined that NGR1 binding to these PM domains is indispensable for NGR1 functionality and relies on cysteine acylation and adjacent polybasic regions as well as on lipid and sterol PM composition. Detailed timing of the early events following graviperception suggested that both NGR1 repolarization and initial auxin asymmetry precede the visible PIN3 polarization. This discrepancy motivated us to unveil a rapid, NGR-dependent translocation of PIN-activating AGCVIII kinase D6PK towards lower PMs of gravity-perceiving cells, thus providing an attractive model for rapid redirection of auxin fluxes following gravistimulation.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

Stochastic representation of the quantum quartic oscillator - Tucci, Gennaro; De Nicola, Stefano; Wald, Sascha; Gambassi, Andrea (SciPost Physics Core)
Recent experimental advances have inspired the development of theoretical tools to describe the non-equilibrium dynamics of quantum systems. Among them an exact representation of quantum spin systems in terms of classical stochastic processes has been proposed. Here we provide first steps towards the extension of this stochastic approach to bosonic systems by considering the one-dimensional quantum quartic oscillator. We show how to exactly parameterize the time evolution of this prototypical model via the dynamics of a set of classical variables. We interpret these variables as stochastic processes, which allows us to propose a novel way to numerically simulate the time evolution of the system. We benchmark our findings by considering analytically solvable limits and providing alternative derivations of known results.
Keywords: Statistical and Nonlinear Physics; Atomic and Molecular Physics; and Optics; Nuclear and High Energy Physics; Condensed Matter Physics

In vitro reconstitution of small GTPase regulation - Loose, Martin; Auer, Albert; Brognara, Gabriel; Budiman, Hanifatul R; Kowalski, Lukasz M; Matijevic, Ivana (FEBS Letters)
Small GTPases play essential roles in the organization of eukaryotic cells. In recent years, it has become clear that their intracellular functions result from intricate biochemical networks of the GTPase and their regulators that dynamically bind to a membrane surface. Due to the inherent complexities of their interactions, however, revealing the underlying mechanisms of action is often difficult to achieve from in vivo studies. This review summarizes in vitro reconstitution approaches developed to obtain a better mechanistic understanding of how small GTPase activities are regulated in space and time.
Keywords: Cell Biology; Genetics; Molecular Biology; Biochemistry; Structural Biology; Biophysics

Witnessing light-driven entanglement using time-resolved resonant inelastic X-ray scattering - Hales, Jordyn; Bajpai, Utkarsh; Liu, Tongtong; Baykusheva, Denitsa Rangelova; Li, Mingda; Mitrano, Matteo; Wang, Yao (Nature Communications)
Characterizing and controlling entanglement in quantum materials is crucial for the development of next-generation quantum technologies. However, defining a quantifiable figure of merit for entanglement in macroscopic solids is theoretically and experimentally challenging. At equilibrium the presence of entanglement can be diagnosed by extracting entanglement witnesses from spectroscopic observables and a nonequilibrium extension of this method could lead to the discovery of novel dynamical phenomena. Here, we propose a systematic approach to quantify the time-dependent quantum Fisher information and entanglement depth of transient states of quantum materials with time-resolved resonant inelastic x-ray scattering. Using a quarter-filled extended Hubbard model as an example, we benchmark the efficiency of this approach and predict a light-enhanced many-body entanglement due to the proximity to a phase boundary. Our work sets the stage for experimentally witnessing and controlling entanglement in light-driven quantum materials via ultrafast spectroscopic measurements.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Evaluating the association of biallelic OGDHL variants with significant phenotypic heterogeneity - Lin, Sheng-Jia; Vona, Barbara; Lau, Tracy; Huang, Kevin; Zaki, Maha S.; Aldeen, Huda Shujaa; Karimiani, Ehsan Ghayoor; Rocca, Clarissa; Noureldeen, Mahmoud M.; Saad, Ahmed K.; Petree, Cassidy; Bartolomaeus, Tobias; et al. (Genome Medicine)
Background: Biallelic variants in OGDHL, encoding part of the α-ketoglutarate dehydrogenase complex, have been associated with highly heterogeneous neurological and neurodevelopmental disorders. However, the validity of this association remains to be confirmed. A second OGDHL patient cohort was recruited to carefully assess the gene-disease relationship. Methods: Using an unbiased genotype-first approach, we screened large, multiethnic aggregated sequencing datasets worldwide for biallelic OGDHL variants. We used CRISPR/Cas9 to generate zebrafish knockouts of ogdhl, ogdh paralogs, and dhtkd1 to investigate functional relationships and impact during development. Functional complementation with patient variant transcripts was conducted to systematically assess protein functionality as a readout for pathogenicity. Results: A cohort of 14 individuals from 12 unrelated families exhibited highly variable clinical phenotypes, with the majority of them presenting at least one additional variant, potentially accounting for a blended phenotype and complicating phenotypic understanding. We also uncovered extreme clinical heterogeneity and high allele frequencies, occasionally incompatible with a fully penetrant recessive disorder. Human cDNA of previously described and new variants were tested in an ogdhl zebrafish knockout model, adding functional evidence for variant reclassification. We disclosed evidence of hypomorphic alleles as well as a loss-of-function variant without deleterious effects in zebrafish variant testing also showing discordant familial segregation, challenging the relationship of OGDHL as a conventional Mendelian gene. Going further, we uncovered evidence for a complex compensatory relationship among OGDH, OGDHL, and DHTKD1 isoenzymes that are associated with neurodevelopmental disorders and exhibit complex transcriptional compensation patterns with partial functional redundancy. Conclusions: Based on the results of genetic, clinical, and functional studies, we formed three hypotheses in which to frame observations: biallelic OGDHL variants lead to a highly variable monogenic disorder, variants in OGDHL are following a complex pattern of inheritance, or they may not be causative at all. Our study further highlights the continuing challenges of assessing the validity of reported disease-gene associations and effects of variants identified in these genes. This is particularly more complicated in making genetic diagnoses based on identification of variants in genes presenting a highly heterogenous phenotype such as “OGDHL-related disorders”.
Keywords: Genetics (clinical); Genetics; Molecular Biology; Molecular Medicine

Sex-specific estimation of cis and trans regulation of gene expression in heads and gonads of Drosophila melanogaster - Puixeu Sala, Gemma; Macon, Ariana; Vicoso, Beatriz (G3: Genes, Genomes, Genetics)
The regulatory architecture of gene expression is known to differ substantially between sexes in Drosophila, but most studies performed so far used whole-body data and only single crosses, which may have limited their scope to detect patterns that are robust across tissues and biological replicates. Here, we use allele-specific gene expression of parental and reciprocal hybrid crosses between 6 Drosophila melanogaster inbred lines to quantify cis- and trans-regulatory variation in heads and gonads of both sexes separately across 3 replicate crosses. Our results suggest that female and male heads, as well as ovaries, have a similar regulatory architecture. On the other hand, testes display more and substantially different cis-regulatory effects, suggesting that sex differences in the regulatory architecture that have been previously observed may largely derive from testis-specific effects. We also examine the difference in cis-regulatory variation of genes across different levels of sex bias in gonads and heads. Consistent with the idea that intersex correlations constrain expression and can lead to sexual antagonism, we find more cis variation in unbiased and moderately biased genes in heads. In ovaries, reduced cis variation is observed for male-biased genes, suggesting that cis variants acting on these genes in males do not lead to changes in ovary expression. Finally, we examine the dominance patterns of gene expression and find that sex- and tissue-specific patterns of inheritance as well as trans-regulatory variation are highly variable across biological crosses, although these were performed in highly controlled experimental conditions. This highlights the importance of using various genetic backgrounds to infer generalizable patterns.
Keywords: Genetics (clinical); Genetics; Molecular Biology

Protocol for sorting cells from mouse brains labeled with mosaic analysis with double markers by flow cytometry - Amberg, Nicole; Cheung, Giselle T; Hippenmeyer, Simon (STAR Protocols)
Mosaic analysis with double markers (MADM) technology enables the generation of genetic mosaic tissue in mice and high-resolution phenotyping at the individual cell level. Here, we present a protocol for isolating MADM-labeled cells with high yield for downstream molecular analyses using fluorescence-activated cell sorting (FACS). We describe steps for generating MADM-labeled mice, perfusion, single-cell suspension, and debris removal. We then detail procedures for cell sorting by FACS and downstream analysis. This protocol is suitable for embryonic to adult mice. For complete details on the use and execution of this protocol, please refer to Contreras et al. (2021).1
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Neuroscience

The impact of chromosomal rearrangements in speciation: From micro- to macroevolution - Lucek, Kay; Giménez, Mabel D.; Joron, Mathieu; Rafajlović, Marina; Searle, Jeremy B.; Walden, Nora; Westram, Anja M; Faria, Rui (Cold Spring Harbor Perspectives in Biology)
Chromosomal rearrangements (CRs) have been known since almost the beginning of genetics. While an important role for CRs in speciation has been suggested, evidence primarily stems from theoretical and empirical studies focusing on the microevolutionary level (i.e., on taxon pairs where speciation is often incomplete). Although the role of CRs in eukaryotic speciation at a macroevolutionary level has been supported by associations between species diversity and rates of evolution of CRs across phylogenies, these findings are limited to a restricted range of CRs and taxa. Now that more broadly applicable and precise CR detection approaches have become available, we address the challenges in filling some of the conceptual and empirical gaps between micro- and macroevolutionary studies on the role of CRs in speciation. We synthesize what is known about the macroevolutionary impact of CRs and suggest new research avenues to overcome the pitfalls of previous studies to gain a more comprehensive understanding of the evolutionary significance of CRs in speciation across the tree of life.
Keywords: General Biochemistry; Genetics and Molecular Biology

Monitoring and active stabilization of laser injection locking using beam ellipticity - Mishra, Umang; Li, Vyacheslav; Wald, Sebastian; Agafonova, Sofya; Diorico, Fritz R; Hosten, Onur (Optics Letters)
We unveil a powerful method for the stabilization of laser injection locking based on sensing variations in the output beam ellipticity of an optically seeded laser. The effect arises due to an interference between the seeding beam and the injected laser output. We demonstrate the method for a commercial semiconductor laser without the need for any internal changes to the readily operational injection locked laser system that was used. The method can also be used to increase the mode-hop free tuning range of lasers, and has the potential to fill a void in the low-noise laser industry.
Keywords: Atomic and Molecular Physics; and Optics

Analog stabilization of an electro-optic I/Q modulator with an auxiliary modulation tone - Wald, Sebastian; Diorico, Fritz R; Hosten, Onur (Applied Optics)
Proper operation of electro-optic I/Q modulators relies on precise adjustment and control of the relative phase biases between the modulator’s internal interferometer arms. We present an all-analog phase bias locking scheme where error signals are obtained from the beat between the optical carrier and optical tones generated by an auxiliary 2 MHz 𝑅𝐹 tone to lock the phases of all three involved interferometers for operation up to 10 GHz. With the developed method, we demonstrate an I/Q modulator in carrier-suppressed single-sideband mode, where the suppressed carrier and sideband are locked at optical power levels <−27dB relative to the transmitted sideband. We describe a simple analytical model for calculating the error signals and detail the implementation of the electronic circuitry for the implementation of the method.
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

LIONESS enables 4D nanoscale reconstruction of living brain tissue - Danzl, Johann G; Velicky, Philipp (Nature Methods)
We developed LIONESS, a technology that leverages improvements to optical super-resolution microscopy and prior information on sample structure via machine learning to overcome the limitations (in 3D-resolution, signal-to-noise ratio and light exposure) of optical microscopy of living biological specimens. LIONESS enables dense reconstruction of living brain tissue and morphodynamics visualization at the nanoscale.
Keywords: Cell Biology; Molecular Biology; Biochemistry; Biotechnology

Real-time monitoring of an endogenous Fgf8a gradient attests to its role as a morphogen during zebrafish gastrulation - Harish, Rohit K; Gupta, Mansi; Zöller, Daniela; Hartmann, Hella; Gheisari, Ali; Machate, Anja; Hans, Stefan; Brand, Michael (Development)
Morphogen gradients impart positional information to cells in a homogenous tissue field. Fgf8a, a highly conserved growth factor, has been proposed to act as a morphogen during zebrafish gastrulation. However, technical limitations have so far prevented direct visualization of the endogenous Fgf8a gradient and confirmation of its morphogenic activity. Here, we monitor Fgf8a propagation in the developing neural plate using a CRISPR/Cas9-mediated EGFP knock-in at the endogenous fgf8a locus. By combining sensitive imaging with single-molecule fluorescence correlation spectroscopy, we demonstrate that Fgf8a, which is produced at the embryonic margin, propagates by diffusion through the extracellular space and forms a graded distribution towards the animal pole. Overlaying the Fgf8a gradient curve with expression profiles of its downstream targets determines the precise input-output relationship of Fgf8a-mediated patterning. Manipulation of the extracellular Fgf8a levels alters the signaling outcome, thus establishing Fgf8a as a bona fide morphogen during zebrafish gastrulation. Furthermore, by hindering Fgf8a diffusion, we demonstrate that extracellular diffusion of the protein from the source is crucial for it to achieve its morphogenic potential.
Keywords: Developmental Biology; Molecular Biology

Phytaspase Is capable of detaching the endoplasmic reticulum retrieval signal from tobacco calreticulin-3 - Teplova, Anastasiia; Pigidanov, Artemii A.; Serebryakova, Marina V.; Golyshev, Sergei A.; Galiullina, Raisa A.; Chichkova, Nina V.; Vartapetian, Andrey B. (International Journal of Molecular Sciences)
Soluble chaperones residing in the endoplasmic reticulum (ER) play vitally important roles in folding and quality control of newly synthesized proteins that transiently pass through the ER en route to their final destinations. These soluble residents of the ER are themselves endowed with an ER retrieval signal that enables the cell to bring the escaped residents back from the Golgi. Here, by using purified proteins, we showed that Nicotiana tabacum phytaspase, a plant aspartate-specific protease, introduces two breaks at the C-terminus of the N. tabacum ER resident calreticulin-3. These cleavages resulted in removal of either a dipeptide or a hexapeptide from the C-terminus of calreticulin-3 encompassing part or all of the ER retrieval signal. Consistently, expression of the calreticulin-3 derivative mimicking the phytaspase cleavage product in Nicotiana benthamiana cells demonstrated loss of the ER accumulation of the protein. Notably, upon its escape from the ER, calreticulin-3 was further processed by an unknown protease(s) to generate the free N-terminal (N) domain of calreticulin-3, which was ultimately secreted into the apoplast. Our study thus identified a specific proteolytic enzyme capable of precise detachment of the ER retrieval signal from a plant ER resident protein, with implications for the further fate of the escaped resident.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Spatial organization and function of RNA molecules within phase-separated condensates in zebrafish are controlled by Dnd1 - Westerich, Kim Joana; Tarbashevich, Katsiaryna; Schick, Jan; Gupta, Antra; Zhu, Mingzhao; Hull, Kenneth; Romo, Daniel; Zeuschner, Dagmar; Goudarzi, Mohammad; Gross-Thebing, Theresa; Raz, Erez (Developmental Cell)
Germ granules, condensates of phase-separated RNA and protein, are organelles that are essential for germline development in different organisms. The patterning of the granules and their relevance for germ cell fate are not fully understood. Combining three-dimensional in vivo structural and functional analyses, we study the dynamic spatial organization of molecules within zebrafish germ granules. We find that the localization of RNA molecules to the periphery of the granules, where ribosomes are localized, depends on translational activity at this location. In addition, we find that the vertebrate-specific Dead end (Dnd1) protein is essential for nanos3 RNA localization at the condensates’ periphery. Accordingly, in the absence of Dnd1, or when translation is inhibited, nanos3 RNA translocates into the granule interior, away from the ribosomes, a process that is correlated with the loss of germ cell fate. These findings highlight the relevance of sub-granule compartmentalization for post-transcriptional control and its importance for preserving germ cell totipotency.
Keywords: Developmental Biology; Cell Biology; General Biochemistry; Genetics and Molecular Biology; Molecular Biology

Large neutral amino acid levels tune perinatal neuronal excitability and survival - Knaus, Lisa; Basilico, Bernadette; Malzl, Daniel; Gerykova Bujalkova, Maria; Smogavec, Mateja; Schwarz, Lena A.; Gorkiewicz, Sarah; Amberg, Nicole; Pauler, Florian; Knittl-Frank, Christian; Tassinari, Marianna; Maulide, Nuno; et al. (Cell)
Little is known about the critical metabolic changes that neural cells have to undergo during development and how temporary shifts in this program can influence brain circuitries and behavior. Inspired by the discovery that mutations in SLC7A5, a transporter of metabolically essential large neutral amino acids (LNAAs), lead to autism, we employed metabolomic profiling to study the metabolic states of the cerebral cortex across different developmental stages. We found that the forebrain undergoes significant metabolic remodeling throughout development, with certain groups of metabolites showing stage-specific changes, but what are the consequences of perturbing this metabolic program? By manipulating Slc7a5 expression in neural cells, we found that the metabolism of LNAAs and lipids are interconnected in the cortex. Deletion of Slc7a5 in neurons affects the postnatal metabolic state, leading to a shift in lipid metabolism. Additionally, it causes stage- and cell-type-specific alterations in neuronal activity patterns, resulting in a long-term circuit dysfunction.
Keywords: General Biochemistry; Genetics and Molecular Biology

Readout of histone methylation by Trim24 locally restricts chromatin opening by p53 - Isbel, Luke; Iskar, Murat; Durdu, Sevi; Weiss, Joscha; Grand, Ralph S.; Hietter-Pfeiffer, Eric; Kozicka, Zuzanna; Michael, Alicia; Burger, Lukas; Thomä, Nicolas H.; Schübeler, Dirk (Nature Structural & Molecular Biology)
The genomic binding sites of the transcription factor (TF) and tumor suppressor p53 are unusually diverse with regard to their chromatin features, including histone modifications, raising the possibility that the local chromatin environment can contextualize p53 regulation. Here, we show that epigenetic characteristics of closed chromatin, such as DNA methylation, do not influence the binding of p53 across the genome. Instead, the ability of p53 to open chromatin and activate its target genes is locally restricted by its cofactor Trim24. Trim24 binds to both p53 and unmethylated histone 3 lysine 4 (H3K4), thereby preferentially localizing to those p53 sites that reside in closed chromatin, whereas it is deterred from accessible chromatin by H3K4 methylation. The presence of Trim24 increases cell viability upon stress and enables p53 to affect gene expression as a function of the local chromatin state. These findings link H3K4 methylation to p53 function and illustrate how specificity in chromatin can be achieved, not by TF-intrinsic sensitivity to histone modifications, but by employing chromatin-sensitive cofactors that locally modulate TF function.
Keywords: Molecular Biology; Structural Biology

The scorpionfly (Panorpa cognata) genome highlights conserved and derived features of the peculiar dipteran X chromosome - Lasne, Clementine; Elkrewi, Marwan N; Toups, Melissa A; Layana Franco, Lorena Alexandra; Macon, Ariana; Vicoso, Beatriz (Molecular Biology and Evolution)
Many insects carry an ancient X chromosome - the Drosophila Muller element F - that likely predates their origin. Interestingly, the X has undergone turnover in multiple fly species (Diptera) after being conserved for more than 450 MY. The long evolutionary distance between Diptera and other sequenced insect clades makes it difficult to infer what could have contributed to this sudden increase in rate of turnover. Here, we produce the first genome and transcriptome of a long overlooked sister-order to Diptera: Mecoptera. We compare the scorpionfly Panorpa cognata X-chromosome gene content, expression, and structure, to that of several dipteran species as well as more distantly-related insect orders (Orthoptera and Blattodea). We find high conservation of gene content between the mecopteran X and the dipteran Muller F element, as well as several shared biological features, such as the presence of dosage compensation and a low amount of genetic diversity, consistent with a low recombination rate. However, the two homologous X chromosomes differ strikingly in their size and number of genes they carry. Our results therefore support a common ancestry of the mecopteran and ancestral dipteran X chromosomes, and suggest that Muller element F shrank in size and gene content after the split of Diptera and Mecoptera, which may have contributed to its turnover in dipteran insects.
Keywords: Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

Quantifying heterologous gene expression during ectopic MazF production in Escherichia coli - Nikolic, Nela; Sauert, Martina; Albanese, Tanino G.; Moll, Isabella (BMC Research Notes)
Objective: MazF is a sequence-specific endoribonuclease-toxin of the MazEF toxin–antitoxin system. MazF cleaves single-stranded ribonucleic acid (RNA) regions at adenine–cytosine–adenine (ACA) sequences in the bacterium Escherichia coli. The MazEF system has been used in various biotechnology and synthetic biology applications. In this study, we infer how ectopic mazF overexpression affects production of heterologous proteins. To this end, we quantified the levels of fluorescent proteins expressed in E. coli from reporters translated from the ACA-containing or ACA-less messenger RNAs (mRNAs). Additionally, we addressed the impact of the 5′-untranslated region of these reporter mRNAs under the same conditions by comparing expression from mRNAs that comprise (canonical mRNA) or lack this region (leaderless mRNA). Results: Flow cytometry analysis indicates that during mazF overexpression, fluorescent proteins are translated from the canonical as well as leaderless mRNAs. Our analysis further indicates that longer mazF overexpression generally increases the concentration of fluorescent proteins translated from ACA-less mRNAs, however it also substantially increases bacterial population heterogeneity. Finally, our results suggest that the strength and duration of mazF overexpression should be optimized for each experimental setup, to maximize the heterologous protein production and minimize the amount of phenotypic heterogeneity in bacterial populations, which is unfavorable in biotechnological processes.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Medicine

Eukaryotic gene regulation at equilibrium, or non? - Zoller, Benjamin; Gregor, Thomas; Tkačik, Gašper (Current Opinion in Systems Biology)
Models of transcriptional regulation that assume equilibrium binding of transcription factors have been less successful at predicting gene expression from sequence in eukaryotes than in bacteria. This could be due to the non-equilibrium nature of eukaryotic regulation. Unfortunately, the space of possible non-equilibrium mechanisms is vast and predominantly uninteresting. The key question is therefore how this space can be navigated efficiently, to focus on mechanisms and models that are biologically relevant. In this review, we advocate for the normative role of theory—theory that prescribes rather than just describes—in providing such a focus. Theory should expand its remit beyond inferring mechanistic models from data, towards identifying non-equilibrium gene regulatory schemes that may have been evolutionarily selected, despite their energy consumption, because they are precise, reliable, fast, or otherwise outperform regulation at equilibrium. We illustrate our reasoning by toy examples for which we provide simulation code.
Keywords: Applied Mathematics; Computer Science Applications; Drug Discovery; General Biochemistry; Genetics and Molecular Biology; Modeling and Simulation

DNA methylation dynamics during germline development - He, Shengbo; Feng, Xiaoqi (Journal of Integrative Plant Biology)
DNA methylation plays essential homeostatic functions in eukaryotic genomes. In animals, DNA methylation is also developmentally regulated and, in turn, regulates development. In the past two decades, huge research effort has endorsed the understanding that DNA methylation plays a similar role in plant development, especially during sexual reproduction. The power of whole-genome sequencing and cell isolation techniques, as well as bioinformatics tools, have enabled recent studies to reveal dynamic changes in DNA methylation during germline development. Furthermore, the combination of these technological advances with genetics, developmental biology and cell biology tools has revealed functional methylation reprogramming events that control gene and transposon activities in flowering plant germlines. In this review, we discuss the major advances in our knowledge of DNA methylation dynamics during male and female germline development in flowering plants.
Keywords: Plant Science; General Biochemistry; Genetics and Molecular Biology; Biochemistry

Polarization-sensitive optoionic membranes from chiral plasmonic nanoparticles - Cai, Jiarong; Zhang, Wei; Xu, Liguang; Hao, Changlong; Ma, Wei; Sun, Maozhong; Wu, Xiaoling; Qin, Xian; Colombari, Felippe Mariano; de Moura, André Farias; Xu, Jiahui; Silva, Mariana Cristina; et al. (Nature Nanotechnology)
Optoelectronic effects differentiating absorption of right and left circularly polarized photons in thin films of chiral materials are typically prohibitively small for their direct photocurrent observation. Chiral metasurfaces increase the electronic sensitivity to circular polarization, but their out-of-plane architecture entails manufacturing and performance trade-offs. Here, we show that nanoporous thin films of chiral nanoparticles enable high sensitivity to circular polarization due to light-induced polarization-dependent ion accumulation at nanoparticle interfaces. Self-assembled multilayers of gold nanoparticles modified with L-phenylalanine generate a photocurrent under right-handed circularly polarized light as high as 2.41 times higher than under left-handed circularly polarized light. The strong plasmonic coupling between the multiple nanoparticles producing planar chiroplasmonic modes facilitates the ejection of electrons, whose entrapment at the membrane–electrolyte interface is promoted by a thick layer of enantiopure phenylalanine. Demonstrated detection of light ellipticity with equal sensitivity at all incident angles mimics phenomenological aspects of polarization vision in marine animals. The simplicity of self-assembly and sensitivity of polarization detection found in optoionic membranes opens the door to a family of miniaturized fluidic devices for chiral photonics.
Keywords: Electrical and Electronic Engineering; Condensed Matter Physics; General Materials Science; Biomedical Engineering; Atomic and Molecular Physics; and Optics; Bioengineering

Structure of respiratory complex I – An emerging blueprint for the mechanism - Kampjut, Domen; Sazanov, Leonid A (Current Opinion in Structural Biology)
Complex I is one of the major respiratory complexes, conserved from bacteria to mammals. It oxidises NADH, reduces quinone and pumps protons across the membrane, thus playing a central role in the oxidative energy metabolism. In this review we discuss our current state of understanding the structure of complex I from various species of mammals, plants, fungi, and bacteria, as well as of several complex I-related proteins. By comparing the structural evidence from these systems in different redox states and data from mutagenesis and molecular simulations, we formulate the mechanisms of electron transfer and proton pumping and explain how they are conformationally and electrostatically coupled. Finally, we discuss the structural basis of the deactivation phenomenon in mammalian complex I.
Keywords: Molecular Biology; Structural Biology

Cryo-electron tomography of the onion cell wall shows bimodally oriented cellulose fibers and reticulated homogalacturonan networks - Nicolas, William J.; Fäßler, Florian; Dutka, Przemysław; Schur, Florian KM; Jensen, Grant; Meyerowitz, Elliot (Current Biology)
One hallmark of plant cells is their cell wall. They protect cells against the environment and high turgor and mediate morphogenesis through the dynamics of their mechanical and chemical properties. The walls are a complex polysaccharidic structure. Although their biochemical composition is well known, how the different components organize in the volume of the cell wall and interact with each other is not well understood and yet is key to the wall’s mechanical properties. To investigate the ultrastructure of the plant cell wall, we imaged the walls of onion (Allium cepa) bulbs in a near-native state via cryo-focused ion beam milling (cryo-FIB milling) and cryo-electron tomography (cryo-ET). This allowed the high-resolution visualization of cellulose fibers in situ. We reveal the coexistence of dense fiber fields bathed in a reticulated matrix we termed “meshing,” which is more abundant at the inner surface of the cell wall. The fibers adopted a regular bimodal angular distribution at all depths in the cell wall and bundled according to their orientation, creating layers within the cell wall. Concomitantly, employing homogalacturonan (HG)-specific enzymatic digestion, we observed changes in the meshing, suggesting that it is—at least in part—composed of HG pectins. We propose the following model for the construction of the abaxial epidermal primary cell wall: the cell deposits successive layers of cellulose fibers at −45° and +45° relative to the cell’s long axis and secretes the surrounding HG-rich meshing proximal to the plasma membrane, which then migrates to more distal regions of the cell wall.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

WDFY3 mutation alters laminar position and morphology of cortical neurons - Schaaf, Zachary A.; Tat, Lyvin; Cannizzaro, Noemi; Green, Ralph; Rülicke, Thomas; Hippenmeyer, Simon; Zarbalis, Konstantinos S. (Molecular Autism)
Background: Proper cerebral cortical development depends on the tightly orchestrated migration of newly born neurons from the inner ventricular and subventricular zones to the outer cortical plate. Any disturbance in this process during prenatal stages may lead to neuronal migration disorders (NMDs), which can vary in extent from focal to global. Furthermore, NMDs show a substantial comorbidity with other neurodevelopmental disorders, notably autism spectrum disorders (ASDs). Our previous work demonstrated focal neuronal migration defects in mice carrying loss-of-function alleles of the recognized autism risk gene WDFY3. However, the cellular origins of these defects in Wdfy3 mutant mice remain elusive and uncovering it will provide critical insight into WDFY3-dependent disease pathology. Methods: Here, in an effort to untangle the origins of NMDs in Wdfy3lacZ mice, we employed mosaic analysis with double markers (MADM). MADM technology enabled us to genetically distinctly track and phenotypically analyze mutant and wild-type cells concomitantly in vivo using immunofluorescent techniques. Results: We revealed a cell autonomous requirement of WDFY3 for accurate laminar positioning of cortical projection neurons and elimination of mispositioned cells during early postnatal life. In addition, we identified significant deviations in dendritic arborization, as well as synaptic density and morphology between wild type, heterozygous, and homozygous Wdfy3 mutant neurons in Wdfy3-MADM reporter mice at postnatal stages. Limitations: While Wdfy3 mutant mice have provided valuable insight into prenatal aspects of ASD pathology that remain inaccessible to investigation in humans, like most animal models, they do not a perfectly replicate all aspects of human ASD biology. The lack of human data makes it indeterminate whether morphological deviations described here apply to ASD patients or some of the other neurodevelopmental conditions associated with WDFY3 mutation. Conclusions: Our genetic approach revealed several cell autonomous requirements of WDFY3 in neuronal development that could underlie the pathogenic mechanisms of WDFY3-related neurodevelopmental conditions. The results are also consistent with findings in other ASD animal models and patients and suggest an important role for WDFY3 in regulating neuronal function and interconnectivity in postnatal life.
Keywords: Psychiatry and Mental health; Developmental Biology; Developmental Neuroscience; Molecular Biology

Heterogeneity of the GFP fitness landscape and data-driven protein design - Gonzalez Somermeyer, Louisa; Fleiss, Aubin; Mishin, Alexander S; Bozhanova, Nina G; Igolkina, Anna A; Meiler, Jens; Alaball Pujol, Maria-Elisenda; Putintseva, Ekaterina V; Sarkisyan, Karen S; Kondrashov, Fyodor (eLife)
Studies of protein fitness landscapes reveal biophysical constraints guiding protein evolution and empower prediction of functional proteins. However, generalisation of these findings is limited due to scarceness of systematic data on fitness landscapes of proteins with a defined evolutionary relationship. We characterized the fitness peaks of four orthologous fluorescent proteins with a broad range of sequence divergence. While two of the four studied fitness peaks were sharp, the other two were considerably flatter, being almost entirely free of epistatic interactions. Mutationally robust proteins, characterized by a flat fitness peak, were not optimal templates for machine-learning-driven protein design – instead, predictions were more accurate for fragile proteins with epistatic landscapes. Our work paves insights for practical application of fitness landscape heterogeneity in protein engineering.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

Relation between the number of peaks and the number of reciprocal sign epistatic interactions - Saona Urmeneta, Raimundo J; Kondrashov, Fyodor; Khudiakova, Kseniia (Bulletin of Mathematical Biology)
Empirical essays of fitness landscapes suggest that they may be rugged, that is having multiple fitness peaks. Such fitness landscapes, those that have multiple peaks, necessarily have special local structures, called reciprocal sign epistasis (Poelwijk et al. in J Theor Biol 272:141–144, 2011). Here, we investigate the quantitative relationship between the number of fitness peaks and the number of reciprocal sign epistatic interactions. Previously, it has been shown (Poelwijk et al. in J Theor Biol 272:141–144, 2011) that pairwise reciprocal sign epistasis is a necessary but not sufficient condition for the existence of multiple peaks. Applying discrete Morse theory, which to our knowledge has never been used in this context, we extend this result by giving the minimal number of reciprocal sign epistatic interactions required to create a given number of peaks.
Keywords: Computational Theory and Mathematics; General Agricultural and Biological Sciences; Pharmacology; General Environmental Science; General Biochemistry; Genetics and Molecular Biology; General Mathematics; Immunology; General Neuroscience

Inversions and parallel evolution - Westram, Anja M; Faria, Rui; Johannesson, Kerstin; Butlin, Roger; Barton, Nicholas H (Philosophical Transactions of the Royal Society B: Biological Sciences)
Local adaptation leads to differences between populations within a species. In many systems, similar environmental contrasts occur repeatedly, sometimes driving parallel phenotypic evolution. Understanding the genomic basis of local adaptation and parallel evolution is a major goal of evolutionary genomics. It is now known that by preventing the break-up of favourable combinations of alleles across multiple loci, genetic architectures that reduce recombination, like chromosomal inversions, can make an important contribution to local adaptation. However, little is known about whether inversions also contribute disproportionately to parallel evolution. Our aim here is to highlight this knowledge gap, to showcase existing studies, and to illustrate the differences between genomic architectures with and without inversions using simple models. We predict that by generating stronger effective selection, inversions can sometimes speed up the parallel adaptive process or enable parallel adaptation where it would be impossible otherwise, but this is highly dependent on the spatial setting. We highlight that further empirical work is needed, in particular to cover a broader taxonomic range and to understand the relative importance of inversions compared to genomic regions without inversions.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

A direct excitatory projection from entorhinal layer 6b neurons to the hippocampus contributes to spatial coding and memory - Ben Simon, Yoav; Käfer, Karola; Velicky, Philipp; Csicsvari, Jozsef L; Danzl, Johann G; Jonas, Peter M (Nature Communications)
The mammalian hippocampal formation (HF) plays a key role in several higher brain functions, such as spatial coding, learning and memory. Its simple circuit architecture is often viewed as a trisynaptic loop, processing input originating from the superficial layers of the entorhinal cortex (EC) and sending it back to its deeper layers. Here, we show that excitatory neurons in layer 6b of the mouse EC project to all sub-regions comprising the HF and receive input from the CA1, thalamus and claustrum. Furthermore, their output is characterized by unique slow-decaying excitatory postsynaptic currents capable of driving plateau-like potentials in their postsynaptic targets. Optogenetic inhibition of the EC-6b pathway affects spatial coding in CA1 pyramidal neurons, while cell ablation impairs not only acquisition of new spatial memories, but also degradation of previously acquired ones. Our results provide evidence of a functional role for cortical layer 6b neurons in the adult brain.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

The human RNA polymerase I structure reveals an HMG-like docking domain specific to metazoans - Daiß, Julia L; Pilsl, Michael; Straub, Kristina; Bleckmann, Andrea; Höcherl, Mona; Heiss, Florian B; Abascal-Palacios, Guillermo; Ramsay, Ewan P; Tluckova, Katarina; Mars, Jean-Clement; Fürtges, Torben; Bruckmann, Astrid; et al. (Life Science Alliance)
Transcription of the ribosomal RNA precursor by RNA polymerase (Pol) I is a major determinant of cellular growth, and dysregulation is observed in many cancer types. Here, we present the purification of human Pol I from cells carrying a genomic GFP fusion on the largest subunit allowing the structural and functional analysis of the enzyme across species. In contrast to yeast, human Pol I carries a single-subunit stalk, and in vitro transcription indicates a reduced proofreading activity. Determination of the human Pol I cryo-EM reconstruction in a close-to-native state rationalizes the effects of disease-associated mutations and uncovers an additional domain that is built into the sequence of Pol I subunit RPA1. This “dock II” domain resembles a truncated HMG box incapable of DNA binding which may serve as a downstream transcription factor–binding platform in metazoans. Biochemical analysis, in situ modelling, and ChIP data indicate that Topoisomerase 2a can be recruited to Pol I via the domain and cooperates with the HMG box domain–containing factor UBF. These adaptations of the metazoan Pol I transcription system may allow efficient release of positive DNA supercoils accumulating downstream of the transcription bubble.
Keywords: Health; Toxicology and Mutagenesis; Plant Science; Biochemistry; Genetics and Molecular Biology (miscellaneous); Ecology

Specification of female germline by microRNA orchestrated auxin signaling in Arabidopsis - Huang, Jian; Zhao, Lei; Malik, Shikha; Gentile, Benjamin R.; Xiong, Va; Arazi, Tzahi; Owen, Heather A.; Friml, Jiří; Zhao, Dazhong (Nature Communications)
Germline determination is essential for species survival and evolution in multicellular organisms. In most flowering plants, formation of the female germline is initiated with specification of one megaspore mother cell (MMC) in each ovule; however, the molecular mechanism underlying this key event remains unclear. Here we report that spatially restricted auxin signaling promotes MMC fate in Arabidopsis. Our results show that the microRNA160 (miR160) targeted gene ARF17 (AUXIN RESPONSE FACTOR17) is required for promoting MMC specification by genetically interacting with the SPL/NZZ (SPOROCYTELESS/NOZZLE) gene. Alterations of auxin signaling cause formation of supernumerary MMCs in an ARF17- and SPL/NZZ-dependent manner. Furthermore, miR160 and ARF17 are indispensable for attaining a normal auxin maximum at the ovule apex via modulating the expression domain of PIN1 (PIN-FORMED1) auxin transporter. Our findings elucidate the mechanism by which auxin signaling promotes the acquisition of female germline cell fate in plants.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Structural and functional basis of mammalian microRNA biogenesis by Dicer - Zapletal, David; Taborska, Eliska; Pasulka, Josef; Malik, Radek; Kubicek, Karel; Zanova, Martina; Much, Christian; Sebesta, Marek; Buccheri, Valeria; Horvat, Filip; Jenickova, Irena; Prochazkova, Michaela; et al. (Molecular Cell)
MicroRNA (miRNA) and RNA interference (RNAi) pathways rely on small RNAs produced by Dicer endonucleases. Mammalian Dicer primarily supports the essential gene-regulating miRNA pathway, but how it is specifically adapted to miRNA biogenesis is unknown. We show that the adaptation entails a unique structural role of Dicer’s DExD/H helicase domain. Although mice tolerate loss of its putative ATPase function, the complete absence of the domain is lethal because it assures high-fidelity miRNA biogenesis. Structures of murine Dicer⋅miRNA precursor complexes revealed that the DExD/H domain has a helicase-unrelated structural function. It locks Dicer in a closed state, which facilitates miRNA precursor selection. Transition to a cleavage-competent open state is stimulated by Dicer-binding protein TARBP2. Absence of the DExD/H domain or its mutations unlocks the closed state, reduces substrate selectivity, and activates RNAi. Thus, the DExD/H domain structurally contributes to mammalian miRNA biogenesis and underlies mechanistical partitioning of miRNA and RNAi pathways.
Keywords: Cell Biology; Molecular Biology

What microglia depletion approaches tell us about the role of microglia on synaptic function and behavior - Basilico, Bernadette; Ferrucci, Laura; Khan, Azka; Di Angelantonio, Silvia; Ragozzino, Davide; Reverte, Ingrid (Frontiers in Cellular Neuroscience)
Microglia are dynamic cells, constantly surveying their surroundings and interacting with neurons and synapses. Indeed, a wealth of knowledge has revealed a critical role of microglia in modulating synaptic transmission and plasticity in the developing brain. In the past decade, novel pharmacological and genetic strategies have allowed the acute removal of microglia, opening the possibility to explore and understand the role of microglia also in the adult brain. In this review, we summarized and discussed the contribution of microglia depletion strategies to the current understanding of the role of microglia on synaptic function, learning and memory, and behavior both in physiological and pathological conditions. We first described the available microglia depletion methods highlighting their main strengths and weaknesses. We then reviewed the impact of microglia depletion on structural and functional synaptic plasticity. Next, we focused our analysis on the effects of microglia depletion on behavior, including general locomotor activity, sensory perception, motor function, sociability, learning and memory both in healthy animals and animal models of disease. Finally, we integrated the findings from the reviewed studies and discussed the emerging roles of microglia on the maintenance of synaptic function, learning, memory strength and forgetfulness, and the implications of microglia depletion in models of brain disease.
Keywords: Cellular and Molecular Neuroscience

Modelling membrane reshaping by staged polymerization of ESCRT-III filaments - Jiang, Xiuyun; Harker-Kirschneck, Lena; Vanhille-Campos, Christian Eduardo; Pfitzner, Anna-Katharina; Lominadze, Elene; Roux, Aurélien; Baum, Buzz; Šarić, Anđela (PLOS Computational Biology)
ESCRT-III filaments are composite cytoskeletal polymers that can constrict and cut cell membranes from the inside of the membrane neck. Membrane-bound ESCRT-III filaments undergo a series of dramatic composition and geometry changes in the presence of an ATP-consuming Vps4 enzyme, which causes stepwise changes in the membrane morphology. We set out to understand the physical mechanisms involved in translating the changes in ESCRT-III polymer composition into membrane deformation. We have built a coarse-grained model in which ESCRT-III polymers of different geometries and mechanical properties are allowed to copolymerise and bind to a deformable membrane. By modelling ATP-driven stepwise depolymerisation of specific polymers, we identify mechanical regimes in which changes in filament composition trigger the associated membrane transition from a flat to a buckled state, and then to a tubule state that eventually undergoes scission to release a small cargo-loaded vesicle. We then characterise how the location and kinetics of polymer loss affects the extent of membrane deformation and the efficiency of membrane neck scission. Our results identify the near-minimal mechanical conditions for the operation of shape-shifting composite polymers that sever membrane necks.
Keywords: Computational Theory and Mathematics; Cellular and Molecular Neuroscience; Genetics; Molecular Biology; Ecology; Modeling and Simulation; Ecology; Evolution; Behavior and Systematics

Editorial: Neuromodulatory ascending systems: Their influence at the microscopic and macroscopic levels - Gambino, Giuditta; Bhik-Ghanie, Rebecca; Giglia, Giuseppe; Puig, M. Victoria; Ramirez Villegas, Juan F; Zaldivar, Daniel (Frontiers in Neural Circuits)
Editorial on the Research Topic
Keywords: Cellular and Molecular Neuroscience; Cognitive Neuroscience; Sensory Systems; Neuroscience (miscellaneous)

Polygenic adaptation after a sudden change in environment - Hayward, Laura; Sella, Guy (eLife)
Polygenic adaptation is thought to be ubiquitous, yet remains poorly understood. Here, we model this process analytically, in the plausible setting of a highly polygenic, quantitative trait that experiences a sudden shift in the fitness optimum. We show how the mean phenotype changes over time, depending on the effect sizes of loci that contribute to variance in the trait, and characterize the allele dynamics at these loci. Notably, we describe the two phases of the allele dynamics: The first is a rapid phase, in which directional selection introduces small frequency differences between alleles whose effects are aligned with or opposed to the shift, ultimately leading to small differences in their probability of fixation during a second, longer phase, governed by stabilizing selection. As we discuss, key results should hold in more general settings and have important implications for efforts to identify the genetic basis of adaptation in humans and other species.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

On the nanoscale structural evolution of solid discharge products in lithium-sulfur batteries using operando scattering - Prehal, Christian; von Mentlen, Jean-Marc; Drvarič Talian, Sara; Vizintin, Alen; Dominko, Robert; Amenitsch, Heinz; Porcar, Lionel; Freunberger, Stefan Alexander; Wood, Vanessa (Nature Communications)
The inadequate understanding of the mechanisms that reversibly convert molecular sulfur (S) into lithium sulfide (Li 2 S) via soluble polysulfides (PSs) formation impedes the development of high-performance lithium-sulfur (Li-S) batteries with non-aqueous electrolyte solutions. Here, we use operando small and wide angle X-ray scattering and operando small angle neutron scattering (SANS) measurements to track the nucleation, growth and dissolution of solid deposits from atomic to sub-micron scales during real-time Li-S cell operation. In particular, stochastic modelling based on the SANS data allows quantifying the nanoscale phase evolution during battery cycling. We show that next to nano-crystalline Li 2 S the deposit comprises solid short-chain PSs particles. The analysis of the experimental data suggests that initially, Li 2 S 2 precipitates from the solution and then is partially converted via solid-state electroreduction to Li 2 S. We further demonstrate that mass transport, rather than electron transport through a thin passivating film, limits the discharge capacity and rate performance in Li-S cells.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Spatiotemporal dynamics of self-organized branching in pancreas-derived organoids - Randriamanantsoa, S.; Papargyriou, A.; Maurer, H. C.; Peschke, K.; Schuster, M.; Zecchin, G.; Steiger, K.; Öllinger, R.; Saur, D.; Scheel, C.; Rad, R.; Hannezo, Edouard B; et al. (Nature Communications)
The development dynamics and self-organization of glandular branched epithelia is of utmost importance for our understanding of diverse processes ranging from normal tissue growth to the growth of cancerous tissues. Using single primary murine pancreatic ductal adenocarcinoma (PDAC) cells embedded in a collagen matrix and adapted media supplementation, we generate organoids that self-organize into highly branched structures displaying a seamless lumen connecting terminal end buds, replicating in vivo PDAC architecture. We identify distinct morphogenesis phases, each characterized by a unique pattern of cell invasion, matrix deformation, protein expression, and respective molecular dependencies. We propose a minimal theoretical model of a branching and proliferating tissue, capturing the dynamics of the first phases. Observing the interaction of morphogenesis, mechanical environment and gene expression in vitro sets a benchmark for the understanding of self-organization processes governing complex organoid structure formation processes and branching morphogenesis.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Muskelin regulates actin-dependent synaptic changes and intrinsic brain activity relevant to behavioral and cognitive processes - Muhia, Mary W; YuanXiang, PingAn; Sedlacik, Jan; Schwarz, Jürgen R.; Heisler, Frank F.; Gromova, Kira V.; Thies, Edda; Breiden, Petra; Pechmann, Yvonne; Kreutz, Michael R.; Kneussel, Matthias (Communications Biology)
Muskelin (Mkln1) is implicated in neuronal function, regulating plasma membrane receptor trafficking. However, its influence on intrinsic brain activity and corresponding behavioral processes remains unclear. Here we show that murine Mkln1 knockout causes non-habituating locomotor activity, increased exploratory drive, and decreased locomotor response to amphetamine. Muskelin deficiency impairs social novelty detection while promoting the retention of spatial reference memory and fear extinction recall. This is strongly mirrored in either weaker or stronger resting-state functional connectivity between critical circuits mediating locomotor exploration and cognition. We show that Mkln1 deletion alters dendrite branching and spine structure, coinciding with enhanced AMPAR-mediated synaptic transmission but selective impairment in synaptic potentiation maintenance. We identify muskelin at excitatory synapses and highlight its role in regulating dendritic spine actin stability. Our findings point to aberrant spine actin modulation and changes in glutamatergic synaptic function as critical mechanisms that contribute to the neurobehavioral phenotype arising from Mkln1 ablation.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology; Medicine (miscellaneous)

Admp regulates tail bending by controlling ventral epidermal cell polarity via phosphorylated myosin localization in Ciona - Kogure, Yuki S.; Muraoka, Hiromochi; Koizumi, Wataru C.; Gelin-alessi, Raphaël; Godard, Benoit G; Oka, Kotaro; Heisenberg, Carl-Philipp J; Hotta, Kohji (Development)
Ventral tail bending, which is transient but pronounced, is found in many chordate embryos and constitutes an interesting model of how tissue interactions control embryo shape. Here, we identify one key upstream regulator of ventral tail bending in embryos of the ascidian Ciona. We show that during the early tailbud stages, ventral epidermal cells exhibit a boat-shaped morphology (boat cell) with a narrow apical surface where phosphorylated myosin light chain (pMLC) accumulates. We further show that interfering with the function of the BMP ligand Admp led to pMLC localizing to the basal instead of the apical side of ventral epidermal cells and a reduced number of boat cells. Finally, we show that cutting ventral epidermal midline cells at their apex using an ultraviolet laser relaxed ventral tail bending. Based on these results, we propose a previously unreported function for Admp in localizing pMLC to the apical side of ventral epidermal cells, which causes the tail to bend ventrally by resisting antero-posterior notochord extension at the ventral side of the tail.
Keywords: Developmental Biology; Molecular Biology

Three-dimensional visualization of planta clathrin-coated vesicles at ultrastructural resolution - Johnson, Alexander J; Kaufmann, Walter; Sommer, Christoph M; Costanzo, Tommaso; Dahhan, Dana A.; Bednarek, Sebastian Y.; Friml, Jiří (Molecular Plant)
Biological systems are the sum of their dynamic three-dimensional (3D) parts. Therefore, it is critical to study biological structures in 3D and at high resolution to gain insights into their physiological functions. Electron microscopy of metal replicas of unroofed cells and isolated organelles has been a key technique to visualize intracellular structures at nanometer resolution. However, many of these methods require specialized equipment and personnel to complete them. Here, we present novel accessible methods to analyze biological structures in unroofed cells and biochemically isolated organelles in 3D and at nanometer resolution, focusing on Arabidopsis clathrin-coated vesicles (CCVs). While CCVs are essential trafficking organelles, their detailed structural information is lacking due to their poor preservation when observed via classical electron microscopy protocols experiments. First, we establish a method to visualize CCVs in unroofed cells using scanning transmission electron microscopy tomography, providing sufficient resolution to define the clathrin coat arrangements. Critically, the samples are prepared directly on electron microscopy grids, removing the requirement to use extremely corrosive acids, thereby enabling the use of this method in any electron microscopy lab. Secondly, we demonstrate that this standardized sample preparation allows the direct comparison of isolated CCV samples with those visualized in cells. Finally, to facilitate the high-throughput and robust screening of metal replicated samples, we provide a deep learning analysis method to screen the “pseudo 3D” morphologies of CCVs imaged with 2D modalities. Collectively, our work establishes accessible ways to examine the 3D structure of biological samples and provide novel insights into the structure of plant CCVs.
Keywords: Plant Science; Molecular Biology

Sequential and additive expression of miR-9 precursors control timing of neurogenesis - Soto, Ximena; Burton, Joshua; Manning, Cerys S.; Minchington, Thomas; Lea, Robert; Lee, Jessica; Kursawe, Jochen; Rattray, Magnus; Papalopulu, Nancy (Development)
MicroRNAs (miRs) have an important role in tuning dynamic gene expression. However, the mechanism by which they are quantitatively controlled is unknown. We show that the amount of mature miR-9, a key regulator of neuronal development, increases during zebrafish neurogenesis in a sharp stepwise manner. We characterize the spatiotemporal profile of seven distinct microRNA primary transcripts (pri-mir)-9s that produce the same mature miR-9 and show that they are sequentially expressed during hindbrain neurogenesis. Expression of late-onset pri-mir-9-1 is added on to, rather than replacing, the expression of early onset pri-mir-9-4 and -9-5 in single cells. CRISPR/Cas9 mutation of the late-onset pri-mir-9-1 prevents the developmental increase of mature miR-9, reduces late neuronal differentiation and fails to downregulate Her6 at late stages. Mathematical modelling shows that an adaptive network containing Her6 is insensitive to linear increases in miR-9 but responds to stepwise increases of miR-9. We suggest that a sharp stepwise increase of mature miR-9 is created by sequential and additive temporal activation of distinct loci. This may be a strategy to overcome adaptation and facilitate a transition of Her6 to a new dynamic regime or steady state.
Keywords: Developmental Biology; Molecular Biology

A feedback loop between lamellipodial extension and HGF-ERK signaling specifies leader cells during collective cell migration - Hino, Naoya; Matsuda, Kimiya; Jikko, Yuya; Maryu, Gembu; Sakai, Katsuya; Imamura, Ryu; Tsukiji, Shinya; Aoki, Kazuhiro; Terai, Kenta; Hirashima, Tsuyoshi; Trepat, Xavier; Matsuda, Michiyuki (Developmental Cell)
Upon the initiation of collective cell migration, the cells at the free edge are specified as leader cells; however, the mechanism underlying the leader cell specification remains elusive. Here, we show that lamellipodial extension after the release from mechanical confinement causes sustained extracellular signal-regulated kinase (ERK) activation and underlies the leader cell specification. Live-imaging of Madin-Darby canine kidney (MDCK) cells and mouse epidermis through the use of Förster resonance energy transfer (FRET)-based biosensors showed that leader cells exhibit sustained ERK activation in a hepatocyte growth factor (HGF)-dependent manner. Meanwhile, follower cells exhibit oscillatory ERK activation waves in an epidermal growth factor (EGF) signaling-dependent manner. Lamellipodial extension at the free edge increases the cellular sensitivity to HGF. The HGF-dependent ERK activation, in turn, promotes lamellipodial extension, thereby forming a positive feedback loop between cell extension and ERK activation and specifying the cells at the free edge as the leader cells. Our findings show that the integration of physical and biochemical cues underlies the leader cell specification during collective cell migration.
Keywords: Developmental Biology; Cell Biology; General Biochemistry; Genetics and Molecular Biology; Molecular Biology

Growth‐mediated negative feedback shapes quantitative antibiotic response - Angermayr, Andreas; Pang, Tin Yau; Chevereau, Guillaume; Mitosch, Karin; Lercher, Martin J; Bollenbach, Mark Tobias (Molecular Systems Biology)
Dose–response relationships are a general concept for quantitatively describing biological systems across multiple scales, from the molecular to the whole-cell level. A clinically relevant example is the bacterial growth response to antibiotics, which is routinely characterized by dose–response curves. The shape of the dose–response curve varies drastically between antibiotics and plays a key role in treatment, drug interactions, and resistance evolution. However, the mechanisms shaping the dose–response curve remain largely unclear. Here, we show in Escherichia coli that the distinctively shallow dose–response curve of the antibiotic trimethoprim is caused by a negative growth-mediated feedback loop: Trimethoprim slows growth, which in turn weakens the effect of this antibiotic. At the molecular level, this feedback is caused by the upregulation of the drug target dihydrofolate reductase (FolA/DHFR). We show that this upregulation is not a specific response to trimethoprim but follows a universal trend line that depends primarily on the growth rate, irrespective of its cause. Rewiring the feedback loop alters the dose–response curve in a predictable manner, which we corroborate using a mathematical model of cellular resource allocation and growth. Our results indicate that growth-mediated feedback loops may shape drug responses more generally and could be exploited to design evolutionary traps that enable selection against drug resistance.
Keywords: Applied Mathematics; Computational Theory and Mathematics; General Agricultural and Biological Sciences; General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; Information Systems

Visualizing maturation factor extraction from the nascent ribosome by the AAA-ATPase Drg1 - Prattes, Michael; Grishkovskaya, Irina; Hodirnau, Victor-Valentin; Hetzmannseder, Christina; Zisser, Gertrude; Sailer, Carolin; Kargas, Vasileios; Loibl, Mathias; Gerhalter, Magdalena; Kofler, Lisa; Warren, Alan J.; Stengel, Florian; et al. (Nature Structural & Molecular Biology)
The AAA-ATPase Drg1 is a key factor in eukaryotic ribosome biogenesis that initiates cytoplasmic maturation of the large ribosomal subunit. Drg1 releases the shuttling maturation factor Rlp24 from pre-60S particles shortly after nuclear export, a strict requirement for downstream maturation. The molecular mechanism of release remained elusive. Here, we report a series of cryo-EM structures that captured the extraction of Rlp24 from pre-60S particles by Saccharomyces cerevisiae Drg1. These structures reveal that Arx1 and the eukaryote-specific rRNA expansion segment ES27 form a joint docking platform that positions Drg1 for efficient extraction of Rlp24 from the pre-ribosome. The tips of the Drg1 N domains thereby guide the Rlp24 C terminus into the central pore of the Drg1 hexamer, enabling extraction by a hand-over-hand translocation mechanism. Our results uncover substrate recognition and processing by Drg1 step by step and provide a comprehensive mechanistic picture of the conserved modus operandi of AAA-ATPases.
Keywords: Molecular Biology; Structural Biology

Fast, high-throughput production of improved rabies viral vectors for specific, efficient and versatile transsynaptic retrograde labeling - Sumser, Anton L; Jösch, Maximilian A; Jonas, Peter M; Ben Simon, Yoav (eLife)
To understand the function of neuronal circuits, it is crucial to disentangle the connectivity patterns within the network. However, most tools currently used to explore connectivity have low throughput, low selectivity, or limited accessibility. Here, we report the development of an improved packaging system for the production of the highly neurotropic RVdGenvA-CVS-N2c rabies viral vectors, yielding titers orders of magnitude higher with no background contamination, at a fraction of the production time, while preserving the efficiency of transsynaptic labeling. Along with the production pipeline, we developed suites of ‘starter’ AAV and bicistronic RVdG-CVS-N2c vectors, enabling retrograde labeling from a wide range of neuronal populations, tailored for diverse experimental requirements. We demonstrate the power and flexibility of the new system by uncovering hidden local and distal inhibitory connections in the mouse hippocampal formation and by imaging the functional properties of a cortical microcircuit across weeks. Our novel production pipeline provides a convenient approach to generate new rabies vectors, while our toolkit flexibly and efficiently expands the current capacity to label, manipulate and image the neuronal activity of interconnected neuronal circuits in vitro and in vivo.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

Direct reciprocity between individuals that use different strategy spaces - Schmid, Laura; Hilbe, Christian; Chatterjee, Krishnendu; Nowak, Martin (PLOS Computational Biology)
In repeated interactions, players can use strategies that respond to the outcome of previous rounds. Much of the existing literature on direct reciprocity assumes that all competing individuals use the same strategy space. Here, we study both learning and evolutionary dynamics of players that differ in the strategy space they explore. We focus on the infinitely repeated donation game and compare three natural strategy spaces: memory-1 strategies, which consider the last moves of both players, reactive strategies, which respond to the last move of the co-player, and unconditional strategies. These three strategy spaces differ in the memory capacity that is needed. We compute the long term average payoff that is achieved in a pairwise learning process. We find that smaller strategy spaces can dominate larger ones. For weak selection, unconditional players dominate both reactive and memory-1 players. For intermediate selection, reactive players dominate memory-1 players. Only for strong selection and low cost-to-benefit ratio, memory-1 players dominate the others. We observe that the supergame between strategy spaces can be a social dilemma: maximum payoff is achieved if both players explore a larger strategy space, but smaller strategy spaces dominate.
Keywords: Computational Theory and Mathematics; Cellular and Molecular Neuroscience; Genetics; Molecular Biology; Ecology; Modeling and Simulation; Ecology; Evolution; Behavior and Systematics

Probing topological phase transitions using high-harmonic generation - Heide, Christian; Kobayashi, Yuki; Baykusheva, Denitsa Rangelova; Jain, Deepti; Sobota, Jonathan A.; Hashimoto, Makoto; Kirchmann, Patrick S.; Oh, Seongshik; Heinz, Tony F.; Reis, David A.; Ghimire, Shambhu (Nature Photonics)
The prediction and realization of topological insulators have sparked great interest in experimental approaches to the classification of materials1,2,3. The phase transition between non-trivial and trivial topological states is important, not only for basic materials science but also for next-generation technology, such as dissipation-free electronics4. It is therefore crucial to develop advanced probes that are suitable for a wide range of samples and environments. Here we demonstrate that circularly polarized laser-field-driven high-harmonic generation is distinctly sensitive to the non-trivial and trivial topological phases in the prototypical three-dimensional topological insulator bismuth selenide5. The phase transition is chemically initiated by reducing the spin–orbit interaction strength through the substitution of bismuth with indium atoms6,7. We find strikingly different high-harmonic responses of trivial and non-trivial topological surface states that manifest themselves as a conversion efficiency and elliptical dichroism that depend both on the driving laser ellipticity and the crystal orientation. The origins of the anomalous high-harmonic response are corroborated by calculations using the semiconductor optical Bloch equations with pairs of surface and bulk bands. As a purely optical approach, this method offers sensitivity to the electronic structure of the material, including its nonlinear response, and is compatible with a wide range of samples and sample environments.
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Microglia control glutamatergic synapses in the adult mouse hippocampus - Basilico, Bernadette; Ferrucci, Laura; Ratano, Patrizia; Golia, Maria T.; Grimaldi, Alfonso; Rosito, Maria; Ferretti, Valentina; Reverte, Ingrid; Sanchini, Caterina; Marrone, Maria C.; Giubettini, Maria; De Turris, Valeria; et al. (Glia)
Microglia cells are active players in regulating synaptic development and plasticity in the brain. However, how they influence the normal functioning of synapses is largely unknown. In this study, we characterized the effects of pharmacological microglia depletion, achieved by administration of PLX5622, on hippocampal CA3-CA1 synapses of adult wild type mice. Following microglial depletion, we observed a reduction of spontaneous and evoked glutamatergic activity associated with a decrease of dendritic spine density. We also observed the appearance of immature synaptic features and higher levels of plasticity. Microglia depleted mice showed a deficit in the acquisition of the Novel Object Recognition task. These events were accompanied by hippocampal astrogliosis, although in the absence ofneuroinflammatory condition. PLX-induced synaptic changes were absent in Cx3cr1−/− mice, highlighting the role of CX3CL1/CX3CR1 axis in microglia control of synaptic functioning. Remarkably, microglia repopulation after PLX5622 withdrawal was associated with the recovery of hippocampal synapses and learning functions. Altogether, these data demonstrate that microglia contribute to normal synaptic functioning in the adult brain and that their removal induces reversible changes in organization and activity of glutamatergic synapses.
Keywords: Cellular and Molecular Neuroscience; Neurology

Specific N-glycans regulate an extracellular adhesion complex during somatosensory dendrite patterning - Rahman, Maisha; Ramirez, Nelson; Diaz‐Balzac, Carlos A; Bülow, Hannes E (EMBO Reports)
N-glycans are molecularly diverse sugars borne by over 70% of proteins transiting the secretory pathway and have been implicated in protein folding, stability, and localization. Mutations in genes important for N-glycosylation result in congenital disorders of glycosylation that are often associated with intellectual disability. Here, we show that structurally distinct N-glycans regulate an extracellular protein complex involved in the patterning of somatosensory dendrites in Caenorhabditis elegans. Specifically, aman-2/Golgi alpha-mannosidase II, a conserved key enzyme in the biosynthesis of specific N-glycans, regulates the activity of the Menorin adhesion complex without obviously affecting the protein stability and localization of its components. AMAN-2 functions cell-autonomously to allow for decoration of the neuronal transmembrane receptor DMA-1/LRR-TM with the correct set of high-mannose/hybrid/paucimannose N-glycans. Moreover, distinct types of N-glycans on specific N-glycosylation sites regulate DMA-1/LRR-TM receptor function, which, together with three other extracellular proteins, forms the Menorin adhesion complex. In summary, specific N-glycan structures regulate dendrite patterning by coordinating the activity of an extracellular adhesion complex, suggesting that the molecular diversity of N-glycans can contribute to developmental specificity in the nervous system.
Keywords: Genetics; Molecular Biology; Biochemistry

Nitrate availability controls translocation of the transcription factor NAC075 for cell-type-specific reprogramming of root growth - Xiao, Huixin; Hu, Yumei; Wang, Yaping; Cheng, Jinkui; Wang, Jinyi; Chen, Guojingwei; Li, Qian; Wang, Shuwei; Wang, Yalu; Wang, Shao-Shuai; Wang, Yi; Xuan, Wei; et al. (Developmental Cell)
Plant root architecture flexibly adapts to changing nitrate (NO3−) availability in the soil; however, the underlying molecular mechanism of this adaptive development remains under-studied. To explore the regulation of NO3−-mediated root growth, we screened for low-nitrate-resistant mutant (lonr) and identified mutants that were defective in the NAC transcription factor NAC075 (lonr1) as being less sensitive to low NO3− in terms of primary root growth. We show that NAC075 is a mobile transcription factor relocating from the root stele tissues to the endodermis based on NO3− availability. Under low-NO3− availability, the kinase CBL-interacting protein kinase 1 (CIPK1) is activated, and it phosphorylates NAC075, restricting its movement from the stele, which leads to the transcriptional regulation of downstream target WRKY53, consequently leading to adapted root architecture. Our work thus identifies an adaptive mechanism involving translocation of transcription factor based on nutrient availability and leading to cell-specific reprogramming of plant root growth.
Keywords: Developmental Biology; Cell Biology; General Biochemistry; Genetics and Molecular Biology; Molecular Biology

Assessing human iPSC-derived microglia identity and function by immunostaining, phagocytosis, calcium activity, and inflammation assay - Hübschmann, Verena; Korkut, Medina; Siegert, Sandra (STAR Protocols)
To understand how potential gene manipulations affect in vitro microglia, we provide a set of short protocols to evaluate microglia identity and function. We detail steps for immunostaining to determine microglia identity. We describe three functional assays for microglia: phagocytosis, calcium response following ATP stimulation, and cytokine expression upon inflammatory stimuli. We apply these protocols to human induced-pluripotent-stem-cell (hiPSC)-derived microglia, but they can be also applied to other in vitro microglial models including primary mouse microglia. For complete details on the use and execution of this protocol, please refer to Bartalska et al. (2022).1
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Neuroscience

In vitro reconstitution of Escherichia coli divisome activation - Radler, Philipp; Baranova, Natalia S.; Dos Santos Caldas, Paulo R; Sommer, Christoph M; Lopez Pelegrin, Maria D; Michalik, David; Loose, Martin (Nature Communications)
The actin-homologue FtsA is essential for E. coli cell division, as it links FtsZ filaments in the Z-ring to transmembrane proteins. FtsA is thought to initiate cell constriction by switching from an inactive polymeric to an active monomeric conformation, which recruits downstream proteins and stabilizes the Z-ring. However, direct biochemical evidence for this mechanism is missing. Here, we use reconstitution experiments and quantitative fluorescence microscopy to study divisome activation in vitro. By comparing wild-type FtsA with FtsA R286W, we find that this hyperactive mutant outperforms FtsA WT in replicating FtsZ treadmilling dynamics, FtsZ filament stabilization and recruitment of FtsN. We could attribute these differences to a faster exchange and denser packing of FtsA R286W below FtsZ filaments. Using FRET microscopy, we also find that FtsN binding promotes FtsA self-interaction. We propose that in the active divisome FtsA and FtsN exist as a dynamic copolymer that follows treadmilling filaments of FtsZ.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

The response of a metapopulation to a changing environment - Barton, Nicholas H; Olusanya, Oluwafunmilola O (Philosophical Transactions of the Royal Society B: Biological Sciences)
A species distributed across diverse environments may adapt to local conditions. We ask how quickly such a species changes its range in response to changed conditions. Szép et al. (Szép E, Sachdeva H, Barton NH. 2021 Polygenic local adaptation in metapopulations: a stochastic eco-evolutionary model. Evolution75, 1030–1045 (doi:10.1111/evo.14210)) used the infinite island model to find the stationary distribution of allele frequencies and deme sizes. We extend this to find how a metapopulation responds to changes in carrying capacity, selection strength, or migration rate when deme sizes are fixed. We further develop a ‘fixed-state’ approximation. Under this approximation, polymorphism is only possible for a narrow range of habitat proportions when selection is weak compared to drift, but for a much wider range otherwise. When rates of selection or migration relative to drift change in a single deme of the metapopulation, the population takes a time of order m−1 to reach the new equilibrium. However, even with many loci, there can be substantial fluctuations in net adaptation, because at each locus, alleles randomly get lost or fixed. Thus, in a finite metapopulation, variation may gradually be lost by chance, even if it would persist in an infinite metapopulation. When conditions change across the whole metapopulation, there can be rapid change, which is predicted well by the fixed-state approximation. This work helps towards an understanding of how metapopulations extend their range across diverse environments. This article is part of the theme issue ‘Species’ ranges in the face of changing environments (Part II)’.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

Evolutionary and structural constraints influencing apolipoprotein A‐I amyloid behavior - Gisonno, Romina A.; Masson, Tomas; Ramella, Nahuel A.; Barrera, Exequiel E.; Romanowski, Víctor; Tricerri, M. Alejandra (Proteins: Structure, Function, and Bioinformatics)
Apolipoprotein A‐I (apoA‐I) has a key function in the reverse cholesterol transport. However, aggregation of apoA‐I single point mutants can lead to hereditary amyloid pathology. Although several studies have tackled the biophysical and structural consequences introduced by these mutations, there is little information addressing the relationship between the evolutionary and structural features that contribute to the amyloid behavior of apoA‐I. We combined evolutionary studies, in silico mutagenesis and molecular dynamics (MD) simulations to provide a comprehensive analysis of the conservation and pathogenic role of the aggregation‐prone regions (APRs) present in apoA‐I. Sequence analysis demonstrated that among the four amyloidogenic regions described for human apoA‐I, only two (APR1 and APR4) are evolutionary conserved across different species of Sarcopterygii. Moreover, stability analysis carried out with the FoldX engine showed that APR1 contributes to the marginal stability of apoA‐I. Structural properties of full‐length apoA‐I models suggest that aggregation is avoided by placing APRs into highly packed and rigid portions of its native fold. Compared to silent variants extracted from the gnomAD database, the thermodynamic and pathogenic impact of amyloid mutations showed evidence of a higher destabilizing effect. MD simulations of the amyloid variant G26R evidenced the partial unfolding of the alpha‐helix bundle with the concomitant exposure of APR1 to the solvent, suggesting an insight into the early steps involved in its aggregation. Our findings highlight APR1 as a relevant component for apoA‐I structural integrity and emphasize a destabilizing effect of amyloid variants that leads to the exposure of this region.
Keywords: Molecular Biology; Biochemistry; Structural Biology

CHD8 haploinsufficiency links autism to transient alterations in excitatory and inhibitory trajectories - Villa, Carlo Emanuele; Cheroni, Cristina; Dotter, Christoph; López-Tóbon, Alejandro; Oliveira, Bárbara; Sacco, Roberto; Yahya, Aysan Çerağ; Morandell, Jasmin; Gabriele, Michele; Tavakoli, Mojtaba; Lyudchik, Julia; Sommer, Christoph M; et al. (Cell Reports)
Mutations in the chromodomain helicase DNA-binding 8 (CHD8) gene are a frequent cause of autism spectrum disorder (ASD). While its phenotypic spectrum often encompasses macrocephaly, implicating cortical abnormalities, how CHD8 haploinsufficiency affects neurodevelopmental is unclear. Here, employing human cerebral organoids, we find that CHD8 haploinsufficiency disrupted neurodevelopmental trajectories with an accelerated and delayed generation of, respectively, inhibitory and excitatory neurons that yields, at days 60 and 120, symmetrically opposite expansions in their proportions. This imbalance is consistent with an enlargement of cerebral organoids as an in vitro correlate of patients’ macrocephaly. Through an isogenic design of patient-specific mutations and mosaic organoids, we define genotype-phenotype relationships and uncover their cell-autonomous nature. Our results define cell-type-specific CHD8-dependent molecular defects related to an abnormal program of proliferation and alternative splicing. By identifying cell-type-specific effects of CHD8 mutations, our study uncovers reproducible developmental alterations that may be employed for neurodevelopmental disease modeling.
Keywords: General Biochemistry; Genetics and Molecular Biology

Identification of long-lived proteins in the mitochondria reveals increased stability of the electron transport chain - Krishna, Shefali; Arrojo e Drigo, Rafael; Capitanio, Juliana S.; Ramachandra, Ranjan; Ellisman, Mark; HETZER, Martin W (Developmental Cell)
In order to combat molecular damage, most cellular proteins undergo rapid turnover. We have previously identified large nuclear protein assemblies that can persist for years in post-mitotic tissues and are subject to age-related decline. Here, we report that mitochondria can be long lived in the mouse brain and reveal that specific mitochondrial proteins have half-lives longer than the average proteome. These mitochondrial long-lived proteins (mitoLLPs) are core components of the electron transport chain (ETC) and display increased longevity in respiratory supercomplexes. We find that COX7C, a mitoLLP that forms a stable contact site between complexes I and IV, is required for complex IV and supercomplex assembly. Remarkably, even upon depletion of COX7C transcripts, ETC function is maintained for days, effectively uncoupling mitochondrial function from ongoing transcription of its mitoLLPs. Our results suggest that modulating protein longevity within the ETC is critical for mitochondrial proteome maintenance and the robustness of mitochondrial function.
Keywords: Developmental Biology; Cell Biology; General Biochemistry; Genetics and Molecular Biology; Molecular Biology

Health and sustainability of glaciers in High Mountain Asia - Miles, Evan; McCarthy, Michael; Dehecq, Amaury; Kneib, Marin; Fugger, Stefan; Pellicciotti, Francesca (Nature Communications)
Glaciers in High Mountain Asia generate meltwater that supports the water needs of 250 million people, but current knowledge of annual accumulation and ablation is limited to sparse field measurements biased in location and glacier size. Here, we present altitudinally-resolved specific mass balances (surface, internal, and basal combined) for 5527 glaciers in High Mountain Asia for 2000–2016, derived by correcting observed glacier thinning patterns for mass redistribution due to ice flow. We find that 41% of glaciers accumulated mass over less than 20% of their area, and only 60% ± 10% of regional annual ablation was compensated by accumulation. Even without 21st century warming, 21% ± 1% of ice volume will be lost by 2100 due to current climatic-geometric imbalance, representing a reduction in glacier ablation into rivers of 28% ± 1%. The ablation of glaciers in the Himalayas and Tien Shan was mostly unsustainable and ice volume in these regions will reduce by at least 30% by 2100. The most important and vulnerable glacier-fed river basins (Amu Darya, Indus, Syr Darya, Tarim Interior) were supplied with >50% sustainable glacier ablation but will see long-term reductions in ice mass and glacier meltwater supply regardless of the Karakoram Anomaly.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Morphology control in crystalline nanoparticle–polymer aggregates - Bian, Tong; Klajn, Rafal (Annals of the New York Academy of Sciences)
Self-assembly of nanoparticles can be mediated by polymers, but has so far led almost exclusively to nanoparticle aggregates that are amorphous. Here, we employed Coulombic interactions to generate a range of composite materials from mixtures of charged nanoparticles and oppositely charged polymers. The assembly behavior of these nanoparticle/polymer composites depends on their order of addition: polymers added to nanoparticles give rise to stable aggregates, but nanoparticles added to polymers disassemble the initially formed aggregates. The amorphous aggregates were transformed into crystalline ones by transiently increasing the ionic strength of the solution. The morphology of the resulting crystals depended on the length of the polymer: short polymer chains mediated the self-assembly of nanoparticles into strongly faceted crystals, whereas long chains led to pseudospherical nanoparticle/polymer assemblies, within which the crystalline order of nanoparticles was retained.
Keywords: History and Philosophy of Science; General Biochemistry; Genetics and Molecular Biology; General Neuroscience

Inducible uniparental chromosome disomy to probe genomic imprinting at single-cell level in brain and beyond - Pauler, Florian; Hudson, Quanah; Laukoter, Susanne; Hippenmeyer, Simon (Neurochemistry International)
Genomic imprinting is an epigenetic mechanism that results in parental allele-specific expression of ~1% of all genes in mouse and human. Imprinted genes are key developmental regulators and play pivotal roles in many biological processes such as nutrient transfer from the mother to offspring and neuronal development. Imprinted genes are also involved in human disease, including neurodevelopmental disorders, and often occur in clusters that are regulated by a common imprint control region (ICR). In extra-embryonic tissues ICRs can act over large distances, with the largest surrounding Igf2r spanning over 10 million base-pairs. Besides classical imprinted expression that shows near exclusive maternal or paternal expression, widespread biased imprinted expression has been identified mainly in brain. In this review we discuss recent developments mapping cell type specific imprinted expression in extra-embryonic tissues and neocortex in the mouse. We highlight the advantages of using an inducible uniparental chromosome disomy (UPD) system to generate cells carrying either two maternal or two paternal copies of a specific chromosome to analyze the functional consequences of genomic imprinting. Mosaic Analysis with Double Markers (MADM) allows fluorescent labeling and concomitant induction of UPD sparsely in specific cell types, and thus to over-express or suppress all imprinted genes on that chromosome. To illustrate the utility of this technique, we explain how MADM-induced UPD revealed new insights about the function of the well-studied Cdkn1c imprinted gene, and how MADM-induced UPDs led to identification of highly cell type specific phenotypes related to perturbed imprinted expression in the mouse neocortex. Finally, we give an outlook on how MADM could be used to probe cell type specific imprinted expression in other tissues in mouse, particularly in extra-embryonic tissues.
Keywords: Cell Biology; Cellular and Molecular Neuroscience

Two linked loci under mutation-selection balance and Muller’s ratchet - Khudiakova, Kseniia; Neretina, Tatiana Yu.; Kondrashov, Alexey S. (Journal of Theoretical Biology)
We report the complete analysis of a deterministic model of deleterious mutations and negative selection against them at two haploid loci without recombination. As long as mutation is a weaker force than selection, mutant alleles remain rare at the only stable equilibrium, and otherwise, a variety of dynamics are possible. If the mutation-free genotype is absent, generally the only stable equilibrium is the one that corresponds to fixation of the mutant allele at the locus where it is less deleterious. This result suggests that fixation of a deleterious allele that follows a click of the Muller’s ratchet is governed by natural selection, instead of random drift.
Keywords: General Biochemistry; Genetics and Molecular Biology; Modelling and Simulation; Statistics and Probability; General Immunology and Microbiology; Applied Mathematics; General Agricultural and Biological Sciences; General Medicine

Structure of the mature Rous sarcoma virus lattice reveals a role for IP6 in the formation of the capsid hexamer - Obr, Martin; Ricana, Clifton L.; Nikulin, Nadia; Feathers, Jon-Philip R.; Klanschnig, Marco; Thader, Andreas; Johnson, Marc C.; Vogt, Volker M.; Schur, Florian KM; Dick, Robert A. (Nature Communications)
Inositol hexakisphosphate (IP6) is an assembly cofactor for HIV-1. We report here that IP6 is also used for assembly of Rous sarcoma virus (RSV), a retrovirus from a different genus. IP6 is ~100-fold more potent at promoting RSV mature capsid protein (CA) assembly than observed for HIV-1 and removal of IP6 in cells reduces infectivity by 100-fold. Here, visualized by cryo-electron tomography and subtomogram averaging, mature capsid-like particles show an IP6-like density in the CA hexamer, coordinated by rings of six lysines and six arginines. Phosphate and IP6 have opposing effects on CA in vitro assembly, inducing formation of T = 1 icosahedrons and tubes, respectively, implying that phosphate promotes pentamer and IP6 hexamer formation. Subtomogram averaging and classification optimized for analysis of pleomorphic retrovirus particles reveal that the heterogeneity of mature RSV CA polyhedrons results from an unexpected, intrinsic CA hexamer flexibility. In contrast, the CA pentamer forms rigid units organizing the local architecture. These different features of hexamers and pentamers determine the structural mechanism to form CA polyhedrons of variable shape in mature RSV particles.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

Structural basis for inhibition of the AAA-ATPase Drg1 by diazaborine - Prattes, Michael; Grishkovskaya, Irina; Hodirnau, Victor-Valentin; Rössler, Ingrid; Klein, Isabella; Hetzmannseder, Christina; Zisser, Gertrude; Gruber, Christian C.; Gruber, Karl; Haselbach, David; Bergler, Helmut (Nature Communications)
The hexameric AAA-ATPase Drg1 is a key factor in eukaryotic ribosome biogenesis and initiates cytoplasmic maturation of the large ribosomal subunit by releasing the shuttling maturation factor Rlp24. Drg1 monomers contain two AAA-domains (D1 and D2) that act in a concerted manner. Rlp24 release is inhibited by the drug diazaborine which blocks ATP hydrolysis in D2. The mode of inhibition was unknown. Here we show the first cryo-EM structure of Drg1 revealing the inhibitory mechanism. Diazaborine forms a covalent bond to the 2′-OH of the nucleotide in D2, explaining its specificity for this site. As a consequence, the D2 domain is locked in a rigid, inactive state, stalling the whole Drg1 hexamer. Resistance mechanisms identified include abolished drug binding and altered positioning of the nucleotide. Our results suggest nucleotide-modifying compounds as potential novel inhibitors for AAA-ATPases.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

Transsynaptic modulation of presynaptic short-term plasticity in hippocampal mossy fiber synapses - Vandael, David H; Okamoto, Yuji; Jonas, Peter M (Nature Communications)
The hippocampal mossy fiber synapse is a key synapse of the trisynaptic circuit. Post-tetanic potentiation (PTP) is the most powerful form of plasticity at this synaptic connection. It is widely believed that mossy fiber PTP is an entirely presynaptic phenomenon, implying that PTP induction is input-specific, and requires neither activity of multiple inputs nor stimulation of postsynaptic neurons. To directly test cooperativity and associativity, we made paired recordings between single mossy fiber terminals and postsynaptic CA3 pyramidal neurons in rat brain slices. By stimulating non-overlapping mossy fiber inputs converging onto single CA3 neurons, we confirm that PTP is input-specific and non-cooperative. Unexpectedly, mossy fiber PTP exhibits anti-associative induction properties. EPSCs show only minimal PTP after combined pre- and postsynaptic high-frequency stimulation with intact postsynaptic Ca2+ signaling, but marked PTP in the absence of postsynaptic spiking and after suppression of postsynaptic Ca2+ signaling (10 mM EGTA). PTP is largely recovered by inhibitors of voltage-gated R- and L-type Ca2+ channels, group II mGluRs, and vacuolar-type H+-ATPase, suggesting the involvement of retrograde vesicular glutamate signaling. Transsynaptic regulation of PTP extends the repertoire of synaptic computations, implementing a brake on mossy fiber detonation and a “smart teacher” function of hippocampal mossy fiber synapses.
Keywords: general physics and astronomy; general biochemistry; genetics and molecular biology; general chemistry

PHF3 regulates neuronal gene expression through the Pol II CTD reader domain SPOC - Appel, Lisa-Marie; Franke, Vedran; Bruno, Melania; Grishkovskaya, Irina; Kasiliauskaite, Aiste; Kaufmann, Tanja; Schoeberl, Ursula E.; Puchinger, Martin G.; Kostrhon, Sebastian; Ebenwaldner, Carmen; Sebesta, Marek; Beltzung, Etienne; et al. (Nature Communications)
The C-terminal domain (CTD) of the largest subunit of RNA polymerase II (Pol II) is a regulatory hub for transcription and RNA processing. Here, we identify PHD-finger protein 3 (PHF3) as a regulator of transcription and mRNA stability that docks onto Pol II CTD through its SPOC domain. We characterize SPOC as a CTD reader domain that preferentially binds two phosphorylated Serine-2 marks in adjacent CTD repeats. PHF3 drives liquid-liquid phase separation of phosphorylated Pol II, colocalizes with Pol II clusters and tracks with Pol II across the length of genes. PHF3 knock-out or SPOC deletion in human cells results in increased Pol II stalling, reduced elongation rate and an increase in mRNA stability, with marked derepression of neuronal genes. Key neuronal genes are aberrantly expressed in Phf3 knock-out mouse embryonic stem cells, resulting in impaired neuronal differentiation. Our data suggest that PHF3 acts as a prominent effector of neuronal gene regulation by bridging transcription with mRNA decay.
Keywords: general physics and astronomy; general biochemistry; genetics and molecular biology; general chemistry

Control of protein synthesis and memory by GluN3A-NMDA receptors through inhibition of GIT1/mTORC1 assembly - Conde-Dusman, María J; Dey, Partha N; Elía-Zudaire, Óscar; Garcia Rabaneda, Luis E; García-Lira, Carmen; Grand, Teddy; Briz, Victor; Velasco, Eric R; Andero Galí, Raül; Niñerola, Sergio; Barco, Angel; Paoletti, Pierre; et al. (eLife)
De novo protein synthesis is required for synapse modifications underlying stable memory encoding. Yet neurons are highly compartmentalized cells and how protein synthesis can be regulated at the synapse level is unknown. Here, we characterize neuronal signaling complexes formed by the postsynaptic scaffold GIT1, the mechanistic target of rapamycin (mTOR) kinase, and Raptor that couple synaptic stimuli to mTOR-dependent protein synthesis; and identify NMDA receptors containing GluN3A subunits as key negative regulators of GIT1 binding to mTOR. Disruption of GIT1/mTOR complexes by enhancing GluN3A expression or silencing GIT1 inhibits synaptic mTOR activation and restricts the mTOR-dependent translation of specific activity-regulated mRNAs. Conversely, GluN3A removal enables complex formation, potentiates mTOR-dependent protein synthesis, and facilitates the consolidation of associative and spatial memories in mice. The memory enhancement becomes evident with light or spaced training, can be achieved by selectively deleting GluN3A from excitatory neurons during adulthood, and does not compromise other aspects of cognition such as memory flexibility or extinction. Our findings provide mechanistic insight into synaptic translational control and reveal a potentially selective target for cognitive enhancement.
Keywords: general immunology and microbiology; general biochemistry; genetics and molecular biology; general medicine; general neuroscience

Cryo-EM structure of a functional monomeric Photosystem I from Thermosynechococcus elongatus reveals red chlorophyll cluster - Çoruh, Mehmet Orkun; Frank, Anna; Tanaka, Hideaki; Kawamoto, Akihiro; El-Mohsnawy, Eithar; Kato, Takayuki; Namba, Keiichi; Gerle, Christoph; Nowaczyk, Marc M.; Kurisu, Genji (Communications Biology)
A high-resolution structure of trimeric cyanobacterial Photosystem I (PSI) from Thermosynechococcus elongatus was reported as the first atomic model of PSI almost 20 years ago. However, the monomeric PSI structure has not yet been reported despite long-standing interest in its structure and extensive spectroscopic characterization of the loss of red chlorophylls upon monomerization. Here, we describe the structure of monomeric PSI from Thermosynechococcus elongatus BP-1. Comparison with the trimer structure gave detailed insights into monomerization-induced changes in both the central trimerization domain and the peripheral regions of the complex. Monomerization-induced loss of red chlorophylls is assigned to a cluster of chlorophylls adjacent to PsaX. Based on our findings, we propose a role of PsaX in the stabilization of red chlorophylls and that lipids of the surrounding membrane present a major source of thermal energy for uphill excitation energy transfer from red chlorophylls to P700.
Keywords: general agricultural and biological Sciences; general biochemistry; genetics and molecular biology; medicine (miscellaneous)

Histone H1 prevents non-CG methylation-mediated small RNA biogenesis in Arabidopsis heterochromatin - Choi, Jaemyung; Lyons, David B; Zilberman, Daniel (eLife)
Flowering plants utilize small RNA molecules to guide DNA methyltransferases to genomic sequences. This RNA-directed DNA methylation (RdDM) pathway preferentially targets euchromatic transposable elements. However, RdDM is thought to be recruited by methylation of histone H3 at lysine 9 (H3K9me), a hallmark of heterochromatin. How RdDM is targeted to euchromatin despite an affinity for H3K9me is unclear. Here we show that loss of histone H1 enhances heterochromatic RdDM, preferentially at nucleosome linker DNA. Surprisingly, this does not require SHH1, the RdDM component that binds H3K9me. Furthermore, H3K9me is dispensable for RdDM, as is CG DNA methylation. Instead, we find that non-CG methylation is specifically associated with small RNA biogenesis, and without H1 small RNA production quantitatively expands to non-CG methylated loci. Our results demonstrate that H1 enforces the separation of euchromatic and heterochromatic DNA methylation pathways by excluding the small RNA-generating branch of RdDM from non-CG methylated heterochromatin.
Keywords: genetics and molecular biology

Loss of Hem1 disrupts macrophage function and impacts migration, phagocytosis, and integrin-mediated adhesion - Stahnke, Stephanie; Döring, Hermann; Kusch, Charly; de Gorter, David J.J.; Dütting, Sebastian; Guledani, Aleks; Pleines, Irina; Schnoor, Michael; Sixt, Michael K; Geffers, Robert; Rohde, Manfred; Müsken, Mathias; et al. (Current Biology)
Hematopoietic-specific protein 1 (Hem1) is an essential subunit of the WAVE regulatory complex (WRC) in immune cells. WRC is crucial for Arp2/3 complex activation and the protrusion of branched actin filament networks. Moreover, Hem1 loss of function in immune cells causes autoimmune diseases in humans. Here, we show that genetic removal of Hem1 in macrophages diminishes frequency and efficacy of phagocytosis as well as phagocytic cup formation in addition to defects in lamellipodial protrusion and migration. Moreover, Hem1-null macrophages displayed strong defects in cell adhesion despite unaltered podosome formation and concomitant extracellular matrix degradation. Specifically, dynamics of both adhesion and de-adhesion as well as concomitant phosphorylation of paxillin and focal adhesion kinase (FAK) were significantly compromised. Accordingly, disruption of WRC function in non-hematopoietic cells coincided with both defects in adhesion turnover and altered FAK and paxillin phosphorylation. Consistently, platelets exhibited reduced adhesion and diminished integrin αIIbβ3 activation upon WRC removal. Interestingly, adhesion phenotypes, but not lamellipodia formation, were partially rescued by small molecule activation of FAK. A full rescue of the phenotype, including lamellipodia formation, required not only the presence of WRCs but also their binding to and activation by Rac. Collectively, our results uncover that WRC impacts on integrin-dependent processes in a FAK-dependent manner, controlling formation and dismantling of adhesions, relevant for properly grabbing onto extracellular surfaces and particles during cell edge expansion, like in migration or phagocytosis.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

Minimal biophysical model of combined antibiotic action - Kavcic, Bor; Tkačik, Gašper; Bollenbach, Tobias (PLOS Computational Biology)
Phenomenological relations such as Ohm’s or Fourier’s law have a venerable history in physics but are still scarce in biology. This situation restrains predictive theory. Here, we build on bacterial “growth laws,” which capture physiological feedback between translation and cell growth, to construct a minimal biophysical model for the combined action of ribosome-targeting antibiotics. Our model predicts drug interactions like antagonism or synergy solely from responses to individual drugs. We provide analytical results for limiting cases, which agree well with numerical results. We systematically refine the model by including direct physical interactions of different antibiotics on the ribosome. In a limiting case, our model provides a mechanistic underpinning for recent predictions of higher-order interactions that were derived using entropy maximization. We further refine the model to include the effects of antibiotics that mimic starvation and the presence of resistance genes. We describe the impact of a starvation-mimicking antibiotic on drug interactions analytically and verify it experimentally. Our extended model suggests a change in the type of drug interaction that depends on the strength of resistance, which challenges established rescaling paradigms. We experimentally show that the presence of unregulated resistance genes can lead to altered drug interaction, which agrees with the prediction of the model. While minimal, the model is readily adaptable and opens the door to predicting interactions of second and higher-order in a broad range of biological systems.
Keywords: Modelling and Simulation; Genetics; Molecular Biology; Antibiotics; Drug interactions

Local genetic context shapes the function of a gene regulatory network - Nagy-Staron, Anna A; Tomasek, Kathrin; Caruso Carter, Caroline; Sonnleitner, Elisabeth; Kavcic, Bor; Paixão, Tiago; Guet, Calin C (eLife)
Gene expression levels are influenced by multiple coexisting molecular mechanisms. Some of these interactions such as those of transcription factors and promoters have been studied extensively. However, predicting phenotypes of gene regulatory networks (GRNs) remains a major challenge. Here, we use a well-defined synthetic GRN to study in Escherichia coli how network phenotypes depend on local genetic context, i.e. the genetic neighborhood of a transcription factor and its relative position. We show that one GRN with fixed topology can display not only quantitatively but also qualitatively different phenotypes, depending solely on the local genetic context of its components. Transcriptional read-through is the main molecular mechanism that places one transcriptional unit (TU) within two separate regulons without the need for complex regulatory sequences. We propose that relative order of individual TUs, with its potential for combinatorial complexity, plays an important role in shaping phenotypes of GRNs.
Keywords: Genetics and Molecular Biology

Reading the chromatinized genome - Michael, Alicia; Thomä, Nicolas H. (Cell)
Eukaryotic DNA-binding proteins operate in the context of chromatin, where nucleosomes are the elementary building blocks. Nucleosomal DNA is wrapped around a histone core, thereby rendering a large fraction of the DNA surface inaccessible to DNA-binding proteins. Nevertheless, first responders in DNA repair and sequence-specific transcription factors bind DNA target sites obstructed by chromatin. While early studies examined protein binding to histone-free DNA, it is only now beginning to emerge how DNA sequences are interrogated on nucleosomes. These readout strategies range from the release of nucleosomal DNA from histones, to rotational/translation register shifts of the DNA motif, and nucleosome-specific DNA binding modes that differ from those observed on naked DNA. Since DNA motif engagement on nucleosomes strongly depends on position and orientation, we argue that motif location and nucleosome positioning co-determine protein access to DNA in transcription and DNA repair.
Keywords: General Biochemistry; Genetics and Molecular Biology

Dynamics of hunchback translation in real-time and at single-mRNA resolution in the Drosophila embryo - Vinter, Daisy J.; Hoppe, Caroline; Minchington, Thomas; Sutcliffe, Catherine; Ashe, Hilary L. (Development)
The Hunchback (Hb) transcription factor is crucial for anterior-posterior patterning of the Drosophila embryo. The maternal hb mRNA acts as a paradigm for translational regulation due to its repression in the posterior of the embryo. However, little is known about the translatability of zygotically transcribed hb mRNAs. Here, we adapt the SunTag system, developed for imaging translation at single-mRNA resolution in tissue culture cells, to the Drosophila embryo to study the translation dynamics of zygotic hb mRNAs. Using single-molecule imaging in fixed and live embryos, we provide evidence for translational repression of zygotic SunTag-hb mRNAs. Whereas the proportion of SunTag-hb mRNAs translated is initially uniform, translation declines from the anterior over time until it becomes restricted to a posterior band in the expression domain. We discuss how regulated hb mRNA translation may help establish the sharp Hb expression boundary, which is a model for precision and noise during developmental patterning. Overall, our data show how use of the SunTag method on fixed and live embryos is a powerful combination for elucidating spatiotemporal regulation of mRNA translation in Drosophila.
Keywords: Developmental Biology; Molecular Biology

The Pleiades are a cluster of fungal effectors that inhibit host defenses - Navarrete, Fernando; Grujic, Nenad; Stirnberg, Alexandra; Saado, Indira; Aleksza, David; Gallei, Michelle C; Adi, Hazem; Alcântara, André; Khan, Mamoona; Bindics, Janos; Trujillo, Marco; Djamei, Armin (PLOS Pathogens)
Biotrophic plant pathogens secrete effector proteins to manipulate the host physiology. Effectors suppress defenses and induce an environment favorable to disease development. Sequence-based prediction of effector function is impeded by their rapid evolution rate. In the maize pathogen Ustilago maydis , effector-coding genes frequently organize in clusters. Here we describe the functional characterization of the pleiades , a cluster of ten effector genes, by analyzing the micro- and macroscopic phenotype of the cluster deletion and expressing these proteins in planta . Deletion of the pleiades leads to strongly impaired virulence and accumulation of reactive oxygen species (ROS) in infected tissue. Eight of the Pleiades suppress the production of ROS upon perception of pathogen associated molecular patterns (PAMPs). Although functionally redundant, the Pleiades target different host components. The paralogs Taygeta1 and Merope1 suppress ROS production in either the cytoplasm or nucleus, respectively. Merope1 targets and promotes the auto-ubiquitination activity of RFI2, a conserved family of E3 ligases that regulates the production of PAMP-triggered ROS burst in plants.
Keywords: Virology; Genetics; Molecular Biology; Immunology; Microbiology; Parasitology

Incomplete removal of extracellular glutamate controls synaptic transmission and integration at a cerebellar synapse - Balmer, Timothy S; Borges Merjane, Carolina; Trussell, Laurence O (eLife)
Synapses of glutamatergic mossy fibers (MFs) onto cerebellar unipolar brush cells (UBCs) generate slow excitatory (ON) or inhibitory (OFF) postsynaptic responses dependent on the complement of glutamate receptors expressed on the UBC’s large dendritic brush. Using mouse brain slice recording and computational modeling of synaptic transmission, we found that substantial glutamate is maintained in the UBC synaptic cleft, sufficient to modify spontaneous firing in OFF UBCs and tonically desensitize AMPARs of ON UBCs. The source of this ambient glutamate was spontaneous, spike-independent exocytosis from the MF terminal, and its level was dependent on activity of glutamate transporters EAAT1–2. Increasing levels of ambient glutamate shifted the polarity of evoked synaptic responses in ON UBCs and altered the phase of responses to in vivo-like synaptic activity. Unlike classical fast synapses, receptors at the UBC synapse are virtually always exposed to a significant level of glutamate, which varies in a graded manner during transmission.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

The CATP-8/P5A-type ATPase functions in multiple pathways during neuronal patterning - Tang, Leo T. H.; Trivedi, Meera; Freund, Jenna; Salazar, Christopher J.; Rahman, Maisha; Ramirez, Nelson; Lee, Garrett; Wang, Yu; Grant, Barth D.; Bülow, Hannes E. (PLOS Genetics)
The assembly of neuronal circuits involves the migrations of neurons from their place of birth to their final location in the nervous system, as well as the coordinated growth and patterning of axons and dendrites. In screens for genes required for patterning of the nervous system, we identified the catp-8/P5A-ATPase as an important regulator of neural patterning. P5A-ATPases are part of the P-type ATPases, a family of proteins known to serve a conserved function as transporters of ions, lipids and polyamines in unicellular eukaryotes, plants, and humans. While the function of many P-type ATPases is relatively well understood, the function of P5A-ATPases in metazoans remained elusive. We show here, that the Caenorhabditis elegans ortholog catp-8/P5A-ATPase is required for defined aspects of nervous system development. Specifically, the catp-8/P5A-ATPase serves functions in shaping the elaborately sculpted dendritic trees of somatosensory PVD neurons. Moreover, catp-8/P5A-ATPase is required for axonal guidance and repulsion at the midline, as well as embryonic and postembryonic neuronal migrations. Interestingly, not all axons at the midline require catp-8/P5A-ATPase , although the axons run in the same fascicles and navigate the same space. Similarly, not all neuronal migrations require catp-8/P5A-ATPase . A CATP-8/P5A-ATPase reporter is localized to the ER in most, if not all, tissues and catp-8/P5A-ATPase can function both cell-autonomously and non-autonomously to regulate neuronal development. Genetic analyses establish that catp-8/P5A-ATPase can function in multiple pathways, including the Menorin pathway, previously shown to control dendritic patterning in PVD, and Wnt signaling, which functions to control neuronal migrations. Lastly, we show that catp-8/P5A-ATPase is required for localizing select transmembrane proteins necessary for dendrite morphogenesis. Collectively, our studies suggest that catp-8/P5A-ATPase serves diverse, yet specific, roles in different genetic pathways and may be involved in the regulation or localization of transmembrane and secreted proteins to specific subcellular compartments.
Keywords: Cancer Research; Genetics (clinical); Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

Reassembling gastrulation - Schauer, Alexandra; Heisenberg, Carl-Philipp J (Developmental Biology)
During development, a single cell is transformed into a highly complex organism through progressive cell division, specification and rearrangement. An important prerequisite for the emergence of patterns within the developing organism is to establish asymmetries at various scales, ranging from individual cells to the entire embryo, eventually giving rise to the different body structures. This becomes especially apparent during gastrulation, when the earliest major lineage restriction events lead to the formation of the different germ layers. Traditionally, the unfolding of the developmental program from symmetry breaking to germ layer formation has been studied by dissecting the contributions of different signaling pathways and cellular rearrangements in the in vivo context of intact embryos. Recent efforts, using the intrinsic capacity of embryonic stem cells to self-assemble and generate embryo-like structures de novo, have opened new avenues for understanding the many ways by which an embryo can be built and the influence of extrinsic factors therein. Here, we discuss and compare divergent and conserved strategies leading to germ layer formation in embryos as compared to in vitro systems, their upstream molecular cascades and the role of extrinsic factors in this process.
Keywords: Developmental Biology; Cell Biology; Molecular Biology

Cul3 regulates cytoskeleton protein homeostasis and cell migration during a critical window of brain development - Morandell, Jasmin; Schwarz, Lena A; Basilico, Bernadette; Tasciyan, Saren; Dimchev, Georgi A; Nicolas, Armel; Sommer, Christoph M; Kreuzinger, Caroline; Dotter, Christoph; Knaus, Lisa; Dobler, Zoe; Cacci, Emanuele; et al. (Nature Communications)
De novo loss of function mutations in the ubiquitin ligase-encoding gene Cullin3 lead to autism spectrum disorder (ASD). In mouse, constitutive haploinsufficiency leads to motor coordination deficits as well as ASD-relevant social and cognitive impairments. However, induction of Cul3 haploinsufficiency later in life does not lead to ASD-relevant behaviors, pointing to an important role of Cul3 during a critical developmental window. Here we show that Cul3 is essential to regulate neuronal migration and, therefore, constitutive Cul3 heterozygous mutant mice display cortical lamination abnormalities. At the molecular level, we found that Cul3 controls neuronal migration by tightly regulating the amount of Plastin3 (Pls3), a previously unrecognized player of neural migration. Furthermore, we found that Pls3 cell-autonomously regulates cell migration by regulating actin cytoskeleton organization, and its levels are inversely proportional to neural migration speed. Finally, we provide evidence that cellular phenotypes associated with autism-linked gene haploinsufficiency can be rescued by transcriptional activation of the intact allele in vitro, offering a proof of concept for a potential therapeutic approach for ASDs.
Keywords: General Biochemistry; Genetics and Molecular Biology

An ESCRT-III polymerization sequence drives membrane deformation and fission - Pfitzner, Anna-Katharina; Mercier, Vincent; Jiang, Xiuyun; Moser von Filseck, Joachim; Baum, Buzz; Šarić, Anđela; Roux, Aurélien (Cell)
The endosomal sorting complex required for transport-III (ESCRT-III) catalyzes membrane fission from within membrane necks, a process that is essential for many cellular functions, from cell division to lysosome degradation and autophagy. How it breaks membranes, though, remains unknown. Here, we characterize a sequential polymerization of ESCRT-III subunits that, driven by a recruitment cascade and by continuous subunit-turnover powered by the ATPase Vps4, induces membrane deformation and fission. During this process, the exchange of Vps24 for Did2 induces a tilt in the polymer-membrane interface, which triggers transition from flat spiral polymers to helical filament to drive the formation of membrane protrusions, and ends with the formation of a highly constricted Did2-Ist1 co-polymer that we show is competent to promote fission when bound on the inside of membrane necks. Overall, our results suggest a mechanism of stepwise changes in ESCRT-III filament structure and mechanical properties via exchange of the filament subunits to catalyze ESCRT-III activity.
Keywords: general biochemistry; genetics and molecular biology

Transcriptional and functional changes of the human microvasculature during physiological aging and Alzheimer disease - Bersini, Simone; Arrojo e Drigo, Rafael; Huang, Ling; Shokhirev, Maxim N.; HETZER, Martin W (Advanced Biosystems)
Aging of the circulatory system correlates with the pathogenesis of a large spectrum of diseases. However, it is largely unknown which factors drive the age-dependent or pathological decline of the vasculature and how vascular defects relate to tissue aging. The goal of the study is to design a multianalytical approach to identify how the cellular microenvironment (i.e., fibroblasts) and serum from healthy donors of different ages or Alzheimer disease (AD) patients can modulate the functionality of organ-specific vascular endothelial cells (VECs). Long-living human microvascular networks embedding VECs and fibroblasts from skin biopsies are generated. RNA-seq, secretome analyses, and microfluidic assays demonstrate that fibroblasts from young donors restore the functionality of aged endothelial cells, an effect also achieved by serum from young donors. New biomarkers of vascular aging are validated in human biopsies and it is shown that young serum induces angiopoietin-like-4, which can restore compromised vascular barriers. This strategy is then employed to characterize transcriptional/functional changes induced on the blood–brain barrier by AD serum, demonstrating the importance of PTP4A3 in the regulation of permeability. Features of vascular degeneration during aging and AD are recapitulated, and a tool to identify novel biomarkers that can be exploited to develop future therapeutics modulating vascular function is established.
Keywords: General Biochemistry; Genetics and Molecular Biology; Biomedical Engineering; Biomaterials

Direct reprogramming of human smooth muscle and vascular endothelial cells reveals defects associated with aging and Hutchinson-Gilford progeria syndrome - Bersini, Simone; Schulte, Roberta; Huang, Ling; Tsai, Hannah; HETZER, Martin W (eLife)
Vascular dysfunctions are a common feature of multiple age-related diseases. However, modeling healthy and pathological aging of the human vasculature represents an unresolved experimental challenge. Here, we generated induced vascular endothelial cells (iVECs) and smooth muscle cells (iSMCs) by direct reprogramming of healthy human fibroblasts from donors of different ages and Hutchinson-Gilford Progeria Syndrome (HGPS) patients. iVECs induced from old donors revealed upregulation of GSTM1 and PALD1, genes linked to oxidative stress, inflammation and endothelial junction stability, as vascular aging markers. A functional assay performed on PALD1 KD VECs demonstrated a recovery in vascular permeability. We found that iSMCs from HGPS donors overexpressed bone morphogenetic protein (BMP)−4, which plays a key role in both vascular calcification and endothelial barrier damage observed in HGPS. Strikingly, BMP4 concentrations are higher in serum from HGPS vs. age-matched mice. Furthermore, targeting BMP4 with blocking antibody recovered the functionality of the vascular barrier in vitro, hence representing a potential future therapeutic strategy to limit cardiovascular dysfunction in HGPS. These results show that iVECs and iSMCs retain disease-related signatures, allowing modeling of vascular aging and HGPS in vitro.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

Nup93 regulates breast tumor growth by modulating cell proliferation and actin cytoskeleton remodeling - Bersini, Simone; Lytle, Nikki K; Schulte, Roberta; Huang, Ling; Wahl, Geoffrey M; HETZER, Martin W (Life Science Alliance)
Nucleoporin 93 (Nup93) expression inversely correlates with the survival of triple-negative breast cancer patients. However, our knowledge of Nup93 function in breast cancer besides its role as structural component of the nuclear pore complex is not understood. Combination of functional assays and genetic analyses suggested that chromatin interaction of Nup93 partially modulates the expression of genes associated with actin cytoskeleton remodeling and epithelial to mesenchymal transition, resulting in impaired invasion of triple-negative, claudin-low breast cancer cells. Nup93 depletion induced stress fiber formation associated with reduced cell migration/proliferation and impaired expression of mesenchymal-like genes. Silencing LIMCH1, a gene responsible for actin cytoskeleton remodeling and up-regulated upon Nup93 depletion, partially restored the invasive phenotype of cancer cells. Loss of Nup93 led to significant defects in tumor establishment/propagation in vivo, whereas patient samples revealed that high Nup93 and low LIMCH1 expression correlate with late tumor stage. Our approach identified Nup93 as contributor of triple-negative, claudin-low breast cancer cell invasion and paves the way to study the role of nuclear envelope proteins during breast cancer tumorigenesis.
Keywords: Health; Toxicology and Mutagenesis; Plant Science; Biochemistry; Genetics and Molecular Biology (miscellaneous); Ecology

The mitochondrial carrier pathway transports non-canonical substrates with an odd number of transmembrane segments - Rampelt, Heike; Sucec, Iva; Bersch, Beate; Horten, Patrick; Perschil, Inge; Martinou, Jean-Claude; van der Laan, Martin; Wiedemann, Nils; Schanda, Paul; Pfanner, Nikolaus (BMC Biology)
Background: The mitochondrial pyruvate carrier (MPC) plays a central role in energy metabolism by transporting pyruvate across the inner mitochondrial membrane. Its heterodimeric composition and homology to SWEET and semiSWEET transporters set the MPC apart from the canonical mitochondrial carrier family (named MCF or SLC25). The import of the canonical carriers is mediated by the carrier translocase of the inner membrane (TIM22) pathway and is dependent on their structure, which features an even number of transmembrane segments and both termini in the intermembrane space. The import pathway of MPC proteins has not been elucidated. The odd number of transmembrane segments and positioning of the N-terminus in the matrix argues against an import via the TIM22 carrier pathway but favors an import via the flexible presequence pathway. Results: Here, we systematically analyzed the import pathways of Mpc2 and Mpc3 and report that, contrary to an expected import via the flexible presequence pathway, yeast MPC proteins with an odd number of transmembrane segments and matrix-exposed N-terminus are imported by the carrier pathway, using the receptor Tom70, small TIM chaperones, and the TIM22 complex. The TIM9·10 complex chaperones MPC proteins through the mitochondrial intermembrane space using conserved hydrophobic motifs that are also required for the interaction with canonical carrier proteins. Conclusions: The carrier pathway can import paired and non-paired transmembrane helices and translocate N-termini to either side of the mitochondrial inner membrane, revealing an unexpected versatility of the mitochondrial import pathway for non-cleavable inner membrane proteins.
Keywords: Biotechnology; Plant Science; General Biochemistry; Genetics and Molecular Biology; Developmental Biology; Cell Biology; Physiology; Ecology; Evolution; Behavior and Systematics; Structural Biology; General Agricultural and Biological Sciences

AXR1 affects DNA methylation independently of its role in regulating meiotic crossover localization - Christophorou, Nicolas; She, Wenjing; Long, Jincheng; Hurel, Aurélie; Beaubiat, Sébastien; Idir, Yassir; Tagliaro-Jahns, Marina; Chambon, Aurélie; Solier, Victor; Vezon, Daniel; Grelon, Mathilde; Feng, Xiaoqi; et al. (PLOS Genetics)
Meiotic crossovers (COs) are important for reshuffling genetic information between homologous chromosomes and they are essential for their correct segregation. COs are unevenly distributed along chromosomes and the underlying mechanisms controlling CO localization are not well understood. We previously showed that meiotic COs are mis-localized in the absence of AXR1, an enzyme involved in the neddylation/rubylation protein modification pathway in Arabidopsis thaliana. Here, we report that in axr1-/-, male meiocytes show a strong defect in chromosome pairing whereas the formation of the telomere bouquet is not affected. COs are also redistributed towards subtelomeric chromosomal ends where they frequently form clusters, in contrast to large central regions depleted in recombination. The CO suppressed regions correlate with DNA hypermethylation of transposable elements (TEs) in the CHH context in axr1-/- meiocytes. Through examining somatic methylomes, we found axr1-/- affects DNA methylation in a plant, causing hypermethylation in all sequence contexts (CG, CHG and CHH) in TEs. Impairment of the main pathways involved in DNA methylation is epistatic over axr1-/- for DNA methylation in somatic cells but does not restore regular chromosome segregation during meiosis. Collectively, our findings reveal that the neddylation pathway not only regulates hormonal perception and CO distribution but is also, directly or indirectly, a major limiting pathway of TE DNA methylation in somatic cells.
Keywords: Cancer Research; Genetics (clinical); Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

Chemical reactivity under nanoconfinement - Grommet, Angela B.; Feller, Moran; Klajn, Rafal (Nature Nanotechnology)
Confining molecules can fundamentally change their chemical and physical properties. Confinement effects are considered instrumental at various stages of the origins of life, and life continues to rely on layers of compartmentalization to maintain an out-of-equilibrium state and efficiently synthesize complex biomolecules under mild conditions. As interest in synthetic confined systems grows, we are realizing that the principles governing reactivity under confinement are the same in abiological systems as they are in nature. In this Review, we categorize the ways in which nanoconfinement effects impact chemical reactivity in synthetic systems. Under nanoconfinement, chemical properties can be modulated to increase reaction rates, enhance selectivity and stabilize reactive species. Confinement effects also lead to changes in physical properties. The fluorescence of light emitters, the colours of dyes and electronic communication between electroactive species can all be tuned under confinement. Within each of these categories, we elucidate design principles and strategies that are widely applicable across a range of confined systems, specifically highlighting examples of different nanocompartments that influence reactivity in similar ways.
Keywords: Electrical and Electronic Engineering; Condensed Matter Physics; General Materials Science; Biomedical Engineering; Atomic and Molecular Physics; and Optics; Bioengineering

Attosecond synchronization of extreme ultraviolet high harmonics from crystals - Vampa, Giulio; Lu, Jian; You, Yong Sing; Baykusheva, Denitsa Rangelova; Wu, Mengxi; Liu, Hanzhe; Schafer, Kenneth J; Gaarde, Mette B; Reis, David A; Ghimire, Shambhu (Journal of Physics B: Atomic, Molecular and Optical Physics)
The interaction of strong near-infrared (NIR) laser pulses with wide-bandgap dielectrics produces high harmonics in the extreme ultraviolet (XUV) wavelength range. These observations have opened up the possibility of attosecond metrology in solids, which would benefit from a precise measurement of the emission times of individual harmonics with respect to the NIR laser field. Here we show that, when high-harmonics are detected from the input surface of a magnesium oxide crystal, a bichromatic probing of the XUV emission shows a clear synchronization largely consistent with a semiclassical model of electron–hole recollisions in bulk solids. On the other hand, the bichromatic spectrogram of harmonics originating from the exit surface of the 200 μm-thick crystal is strongly modified, indicating the influence of laser field distortions during propagation. Our tracking of sub-cycle electron and hole re-collisions at XUV energies is relevant to the development of solid-state sources of attosecond pulses.
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics

Converting microwave and telecom photons with a silicon photonic nanomechanical interface - Arnold, Georg M; Wulf, Matthias; Barzanjeh, Shabir; Redchenko, Elena; Rueda Sanchez, Alfredo R; Hease, William J; Hassani, Farid; Fink, Johannes M (Nature Communications)
Practical quantum networks require low-loss and noise-resilient optical interconnects as well as non-Gaussian resources for entanglement distillation and distributed quantum computation. The latter could be provided by superconducting circuits but existing solutions to interface the microwave and optical domains lack either scalability or efficiency, and in most cases the conversion noise is not known. In this work we utilize the unique opportunities of silicon photonics, cavity optomechanics and superconducting circuits to demonstrate a fully integrated, coherent transducer interfacing the microwave X and the telecom S bands with a total (internal) bidirectional transduction efficiency of 1.2% (135%) at millikelvin temperatures. The coupling relies solely on the radiation pressure interaction mediated by the femtometer-scale motion of two silicon nanobeams reaching a V π as low as 16 μV for sub-nanowatt pump powers. Without the associated optomechanical gain, we achieve a total (internal) pure conversion efficiency of up to 0.019% (1.6%), relevant for future noise-free operation on this qubit-compatible platform.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

Oncogenic state and cell identity combinatorially dictate the susceptibility of cells within glioma development hierarchy to IGF1R targeting - Tian, Anhao; Kang, Bo; Li, Baizhou; Qiu, Biying; Jiang, Wenhong; Shao, Fangjie; Gao, Qingqing; Liu, Rui; Cai, Chengwei; Jing, Rui; Wang, Wei; Chen, Pengxiang; et al. (Advanced Science)
Glioblastoma is the most malignant cancer in the brain and currently incurable. It is urgent to identify effective targets for this lethal disease. Inhibition of such targets should suppress the growth of cancer cells and, ideally also precancerous cells for early prevention, but minimally affect their normal counterparts. Using genetic mouse models with neural stem cells (NSCs) or oligodendrocyte precursor cells (OPCs) as the cells‐of‐origin/mutation, it is shown that the susceptibility of cells within the development hierarchy of glioma to the knockout of insulin‐like growth factor I receptor (IGF1R) is determined not only by their oncogenic states, but also by their cell identities/states. Knockout of IGF1R selectively disrupts the growth of mutant and transformed, but not normal OPCs, or NSCs. The desirable outcome of IGF1R knockout on cell growth requires the mutant cells to commit to the OPC identity regardless of its development hierarchical status. At the molecular level, oncogenic mutations reprogram the cellular network of OPCs and force them to depend more on IGF1R for their growth. A new‐generation brain‐penetrable, orally available IGF1R inhibitor harnessing tumor OPCs in the brain is also developed. The findings reveal the cellular window of IGF1R targeting and establish IGF1R as an effective target for the prevention and treatment of glioblastoma.
Keywords: General Engineering; General Physics and Astronomy; General Materials Science; Medicine (miscellaneous); General Chemical Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous)

Persistent and reversible solid iodine electrodeposition in nanoporous carbons - Prehal, Christian; Fitzek, Harald; Kothleitner, Gerald; Presser, Volker; Gollas, Bernhard; Freunberger, Stefan Alexander; Abbas, Qamar (Nature Communications)
Aqueous iodine based electrochemical energy storage is considered a potential candidate to improve sustainability and performance of current battery and supercapacitor technology. It harnesses the redox activity of iodide, iodine, and polyiodide species in the confined geometry of nanoporous carbon electrodes. However, current descriptions of the electrochemical reaction mechanism to interconvert these species are elusive. Here we show that electrochemical oxidation of iodide in nanoporous carbons forms persistent solid iodine deposits. Confinement slows down dissolution into triiodide and pentaiodide, responsible for otherwise significant self-discharge via shuttling. The main tools for these insights are in situ Raman spectroscopy and in situ small and wide-angle X-ray scattering (in situ SAXS/WAXS). In situ Raman confirms the reversible formation of triiodide and pentaiodide. In situ SAXS/WAXS indicates remarkable amounts of solid iodine deposited in the carbon nanopores. Combined with stochastic modeling, in situ SAXS allows quantifying the solid iodine volume fraction and visualizing the iodine structure on 3D lattice models at the sub-nanometer scale. Based on the derived mechanism, we demonstrate strategies for improved iodine pore filling capacity and prevention of self-discharge, applicable to hybrid supercapacitors and batteries.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

Cysteine oxidation and disulfide formation in the ribosomal exit tunnel - Schulte, Linda; Mao, Jiafei; Reitz, Julian; Sreeramulu, Sridhar; Kudlinzki, Denis; Hodirnau, Victor-Valentin; Meier-Credo, Jakob; Saxena, Krishna; Buhr, Florian; Langer, Julian D.; Blackledge, Martin; Frangakis, Achilleas S.; et al. (Nature Communications)
Understanding the conformational sampling of translation-arrested ribosome nascent chain complexes is key to understand co-translational folding. Up to now, coupling of cysteine oxidation, disulfide bond formation and structure formation in nascent chains has remained elusive. Here, we investigate the eye-lens protein γB-crystallin in the ribosomal exit tunnel. Using mass spectrometry, theoretical simulations, dynamic nuclear polarization-enhanced solid-state nuclear magnetic resonance and cryo-electron microscopy, we show that thiol groups of cysteine residues undergo S-glutathionylation and S-nitrosylation and form non-native disulfide bonds. Thus, covalent modification chemistry occurs already prior to nascent chain release as the ribosome exit tunnel provides sufficient space even for disulfide bond formation which can guide protein folding.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

The Moran process on 2-chromatic graphs - Kaveh, Kamran; McAvoy, Alex; Chatterjee, Krishnendu; Nowak, Martin A. (PLOS Computational Biology)
Resources are rarely distributed uniformly within a population. Heterogeneity in the concentration of a drug, the quality of breeding sites, or wealth can all affect evolutionary dynamics. In this study, we represent a collection of properties affecting the fitness at a given location using a color. A green node is rich in resources while a red node is poorer. More colors can represent a broader spectrum of resource qualities. For a population evolving according to the birth-death Moran model, the first question we address is which structures, identified by graph connectivity and graph coloring, are evolutionarily equivalent. We prove that all properly two-colored, undirected, regular graphs are evolutionarily equivalent (where “properly colored” means that no two neighbors have the same color). We then compare the effects of background heterogeneity on properly two-colored graphs to those with alternative schemes in which the colors are permuted. Finally, we discuss dynamic coloring as a model for spatiotemporal resource fluctuations, and we illustrate that random dynamic colorings often diminish the effects of background heterogeneity relative to a proper two-coloring.
Keywords: Ecology; Modelling and Simulation; Computational Theory and Mathematics; Genetics; Ecology; Evolution; Behavior and Systematics; Molecular Biology; Cellular and Molecular Neuroscience

Cryo-electron tomography structure of Arp2/3 complex in cells reveals new insights into the branch junction - Fäßler, Florian; Dimchev, Georgi A; Hodirnau, Victor-Valentin; Wan, William; Schur, Florian KM (Nature Communications)
The actin-related protein (Arp)2/3 complex nucleates branched actin filament networks pivotal for cell migration, endocytosis and pathogen infection. Its activation is tightly regulated and involves complex structural rearrangements and actin filament binding, which are yet to be understood. Here, we report a 9.0 Å resolution structure of the actin filament Arp2/3 complex branch junction in cells using cryo-electron tomography and subtomogram averaging. This allows us to generate an accurate model of the active Arp2/3 complex in the branch junction and its interaction with actin filaments. Notably, our model reveals a previously undescribed set of interactions of the Arp2/3 complex with the mother filament, significantly different to the previous branch junction model. Our structure also indicates a central role for the ArpC3 subunit in stabilizing the active conformation.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Physics and Astronomy; General Chemistry

SCIM: Universal single-cell matching with unpaired feature sets - Stark, Stefan G; Ficek, Joanna; Locatello, Francesco; Bonilla, Ximena; Chevrier, Stéphane; Singer, Franziska; Aebersold, Rudolf; Al-Quaddoomi, Faisal S; Albinus, Jonas; Alborelli, Ilaria; Andani, Sonali; Attinger, Per-Olof; et al. (Bioinformatics)
Motivation: Recent technological advances have led to an increase in the production and availability of single-cell data. The ability to integrate a set of multi-technology measurements would allow the identification of biologically or clinically meaningful observations through the unification of the perspectives afforded by each technology. In most cases, however, profiling technologies consume the used cells and thus pairwise correspondences between datasets are lost. Due to the sheer size single-cell datasets can acquire, scalable algorithms that are able to universally match single-cell measurements carried out in one cell to its corresponding sibling in another technology are needed. Results: We propose Single-Cell data Integration via Matching (SCIM), a scalable approach to recover such correspondences in two or more technologies. SCIM assumes that cells share a common (low-dimensional) underlying structure and that the underlying cell distribution is approximately constant across technologies. It constructs a technology-invariant latent space using an autoencoder framework with an adversarial objective. Multi-modal datasets are integrated by pairing cells across technologies using a bipartite matching scheme that operates on the low-dimensional latent representations. We evaluate SCIM on a simulated cellular branching process and show that the cell-to-cell matches derived by SCIM reflect the same pseudotime on the simulated dataset. Moreover, we apply our method to two real-world scenarios, a melanoma tumor sample and a human bone marrow sample, where we pair cells from a scRNA dataset to their sibling cells in a CyTOF dataset achieving 90% and 78% cell-matching accuracy for each one of the samples, respectively.
Keywords: Computational Mathematics; Computational Theory and Mathematics; Computer Science Applications; Molecular Biology; Biochemistry; Statistics and Probability

TOLs function as ubiquitin receptors in the early steps of the ESCRT pathway in higher plants - Moulinier-Anzola, Jeanette; Schwihla, Maximilian; De-Araújo, Lucinda; Artner, Christina; Jörg, Lisa; Konstantinova, Nataliia; Luschnig, Christian; Korbei, Barbara (Molecular Plant)
Protein abundance and localization at the plasma membrane (PM) shapes plant development and mediates adaptation to changing environmental conditions. It is regulated by ubiquitination, a post-translational modification crucial for the proper sorting of endocytosed PM proteins to the vacuole for subsequent degradation. To understand the significance and the variety of roles played by this reversible modification, the function of ubiquitin receptors, which translate the ubiquitin signature into a cellular response, needs to be elucidated. In this study, we show that TOL (TOM1-like) proteins function in plants as multivalent ubiquitin receptors, governing ubiquitinated cargo delivery to the vacuole via the conserved Endosomal Sorting Complex Required for Transport (ESCRT) pathway. TOL2 and TOL6 interact with components of the ESCRT machinery and bind to K63-linked ubiquitin via two tandemly arranged conserved ubiquitin-binding domains. Mutation of these domains results not only in a loss of ubiquitin binding but also altered localization, abolishing TOL6 ubiquitin receptor activity. Function and localization of TOL6 is itself regulated by ubiquitination, whereby TOL6 ubiquitination potentially modulates degradation of PM-localized cargoes, assisting in the fine-tuning of the delicate interplay between protein recycling and downregulation. Taken together, our findings demonstrate the function and regulation of a ubiquitin receptor that mediates vacuolar degradation of PM proteins in higher plants.
Keywords: Plant Science; Molecular Biology

Molecular recognition at septin interfaces: The switches hold the key - Rosa, Higor Vinícius Dias; Leonardo, Diego Antonio; Brognara, Gabriel; Brandão-Neto, José; D'Muniz Pereira, Humberto; Araújo, Ana Paula Ulian; Garratt, Richard Charles (Journal of Molecular Biology)
The assembly of a septin filament requires that homologous monomers must distinguish between one another in establishing appropriate interfaces with their neighbors. To understand this phenomenon at the molecular level, we present the first four crystal structures of heterodimeric septin complexes. We describe in detail the two distinct types of G-interface present within the octameric particles, which must polymerize to form filaments. These are formed between SEPT2 and SEPT6 and between SEPT7 and SEPT3, and their description permits an understanding of the structural basis for the selectivity necessary for correct filament assembly. By replacing SEPT6 by SEPT8 or SEPT11, it is possible to rationalize Kinoshita's postulate, which predicts the exchangeability of septins from within a subgroup. Switches I and II, which in classical small GTPases provide a mechanism for nucleotide-dependent conformational change, have been repurposed in septins to play a fundamental role in molecular recognition. Specifically, it is switch I which holds the key to discriminating between the two different G-interfaces. Moreover, residues which are characteristic for a given subgroup play subtle, but pivotal, roles in guaranteeing that the correct interfaces are formed.
Keywords: Molecular Biology; Structural Biology